Lamination of white film and recorded material
By providing a polymer layer incompatible with polyester on the polyester film to form a laminated white film, the problem of melting and wrinkling of synthetic paper in high temperature environment is solved, and stable printing and easy reuse effect is achieved at high temperature.
Patent Information
- Application Number
- CN202210350855.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-11-14
- Filing Date
- 2018-03-02
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2038-03-02
AI Technical Summary
In the prior art, synthetic paper is not resistant to heat and is prone to melting and wrinkles when used in a copier or other equipment, resulting in a decrease in image quality and blockage of the equipment.
A polyester film containing an antistatic agent is used as a base material, and a polymer layer incompatible with the polyester is provided on its surface to form a laminated white film. The film has good printing properties and easy peeling and removing image-forming substances.
It is achieved that it is not easy to melt and wrinkle in high temperature environments, maintains image quality and reduces the risk of equipment blockage, and has good antistatic properties and easy reuse.
Smart Images

Figure BDA0003580156730000151 
Figure BDA0003580156730000531 
Figure BDA0003580156730000611
Abstract
Description
[0001] This application is a divisional application of an application with a filing date of March 2, 2018, application number 201880011701.1, and invention name “Laminated white film and recorded material”. Technical Field
[0002] The present invention relates to a laminated white film and more particularly to a plastic sheet suitable as an information printing medium, that is, a recording material, in place of paper such as copy paper. Background Art
[0003] At present, with the improvement of the performance of copy machines and printers, these devices are not only used for printing and copying documents, but also for printing photos and images, issuing bills and vouchers, etc., and issuing paper materials for various purposes and forms. As a result, the consumption of copy paper and printing paper in enterprises and households has increased.
[0004] From the viewpoint of suppressing deforestation, large-scale consumption of paper including copy paper and printer paper is not desirable, and therefore, recycled paper that is obtained by collecting used paper and separating it into recycled pulp at a paper mill and then reusing it has come to be used.
[0005] Recycled paper is the recycled used paper as its main raw material. However, in order to make recycled paper from the recycled used paper, a certain amount of new wood resources are required. Assuming that the utilization rate of recycled paper is improved, wood resources are still consumed, and the use of recycled paper is not a fundamental solution for protecting the forest environment. In addition, energy is required in the recycling process, so there are also problems from the perspective of energy conservation.
[0006] Furthermore, recycled paper is still inferior in quality to high-quality paper. When copy paper made of recycled paper is used, the whiteness of the paper decreases and the color tone sometimes turns gray. Therefore, the degree of color development during printing decreases and there is a tendency for image quality to deteriorate.
[0007] Furthermore, recycled paper has manufacturing costs and tends to be more expensive than high-quality paper.
[0008] Due to these various problems, it has not been determined that the paper is actually used as a substitute for high-quality paper.
[0009] Instead of such recycled paper, it is proposed that the image formed on the surface of the paper by an electronic photographic method such as a copier be peeled off and removed, thereby enabling the reuse of the paper that has been used. For example, a recyclable recording material is disclosed, which uses a paper mainly composed of cellulose fibers as a base, and a polymer selected from polyvinyl alcohol, starch, carboxymethyl cellulose, polyvinyl acetate, and acrylic resin is provided on the recording image surface of the base, and a layer containing a compound having a linear or branched alkyl or alkenyl group and having a toner repellent property is provided on the layer containing the polymer (for example, refer to Patent Document 1).
[0010] However, the above-mentioned recorded material has a thinner polymer layer in order to reduce the cost of the polymer layer, but it still needs a paper structure as the basis, and it is impossible to completely avoid using wood resources, so it is not a solution for protecting the forest environment. In addition, based on the use of paper, the recorded image penetrates into the fiber of the paper, so the peeling and removal performance becomes insufficient.
[0011] Therefore, there is research on synthetic paper made of plastic as a material that completely replaces paper. For example, synthetic paper made of polypropylene is used in daily necessities. (For example, refer to Patent Document 2)
[0012] Prior art literature
[0013] Patent Literature
[0014] Patent Document 1: Japanese Patent Application Publication No. 2005-234162
[0015] Patent Document 2: Japanese Patent Application Laid-Open No. 10-204196 Summary of the invention
[0016] Problem that the invention aims to solve
[0017] However, the synthetic paper described in Patent Document 2 is not heat-resistant. If used in a copier or printer that performs toner fixing at a relatively high temperature, the synthetic paper may melt inside the copier and wrinkle, which may cause a paper jam.
[0018] The present invention is made in view of the above actual situation, and the problem to be solved is to provide a laminated white film that can be used as an information printing medium, i.e., a recording material, instead of paper such as copy paper, and is extremely cost-effective. In addition, it is also a problem of the present invention to reduce the clogging of the film during the conveying process of the recording material such as copy paper or printing paper in a copier.
[0019] Solutions for solving problems
[0020] The main purpose of the present invention is a laminated white film, characterized in that the apparent density is 0.7 to 1.3 g / cm 3 A polyester film having a thickness of 10 to 1000 μm has a functional layer containing an antistatic agent on at least one surface thereof, and the polyester film contains a polymer incompatible with polyester.
[0021] Effects of the Invention
[0022] The laminated white film of the present invention is a film made of the following plastics: the polyester film as a base material contains a polymer incompatible with the polyester in addition to the polyester, so that it can be used as an information printing medium, i.e., a recording material, instead of paper such as copy paper, and is extremely cost-effective. Furthermore, the laminated white film of the present invention can be suitable for transferring toner images. That is, by transferring the toner image to the recording material by an electronic photograph method, a thermal transfer method, etc., it can be suitable for transferring the toner image. In addition, after being used as a recording material, the text and image generated by the image forming material formed on the surface can be easily peeled off and removed.
[0023] Furthermore, since the functional layer containing the antistatic agent is provided on at least one surface of the polyester film, clogging of the film during the conveyance process of the recording material such as copy paper or printing paper in the copier can be reduced.
[0024] Furthermore, the functional layer contains a release agent, so that after being used as a recording material, the characters and images formed by the image forming material containing a thermoplastic resin on the surface can be easily peeled off and removed, so that it can be reused. In this way, a film having both the property of transferring a toner image, that is, the property of fixing the image forming material to the film substrate, and the opposite property, that is, the property of peeling the image forming material from the film substrate can be formed. DETAILED DESCRIPTION
[0025] Hereinafter, the present invention will be described in further detail.
[0026] <<First embodiment>>
[0027] As an example of the first embodiment for carrying out the present invention, a laminated white film 1 including a functional layer containing an antistatic agent on at least one surface of a polyester film as a substrate (referred to as “the present laminated white film 1 ”) will be described.
[0028] <Polyester film>
[0029] The polyester film serving as the base material of the laminated white film 1 preferably includes a polyester resin layer containing at least polyester as a main component resin and a polymer incompatible with the polyester.
[0030] Here, the "main component resin" refers to the resin with the largest proportion in the resin components constituting the polyester resin layer. It can be assumed that the main component resin accounts for 30% by mass or more, 50% by mass or more, and 80% by mass or more (including 100% by mass) in the resin components constituting the polyester resin layer.
[0031] The polyester film may be a single layer formed of the polyester resin layer, or may be a multilayer having two, three, four or more layers of a polyester resin layer, without particular limitation. That is, when the polyester film is a single layer, the polyester film refers to the polyester resin layer itself. In addition, when the polyester film is a multilayer having two or more layers, all layers may be polyester resin layers, or one or more layers may be resin layers other than polyester. It is particularly preferred that all layers are polyester resin layers.
[0032] Among them, the polyester film is preferably laminated in two or more layers, and more preferably has a three-layer structure consisting of two surface layers and an intermediate layer (surface layer / intermediate layer / surface layer).
[0033] The laminated structure of two layers refers to a structure of two surface layers, and specifically includes a structure of two layers having different compositions such as the type of polyester constituting each layer and the particles contained therein.
[0034] (Polyester)
[0035] The polyester film as the substrate, in particular, the polyester constituting the polyester resin layer may be obtained by polycondensation of an aromatic dicarboxylic acid and an aliphatic diol.
[0036] Examples of the aromatic dicarboxylic acid include terephthalic acid, isophthalic acid, and 2,6-naphthalene dicarboxylic acid. Examples of the aliphatic diol include ethylene glycol, diethylene glycol, trimethylene glycol, tetramethylene glycol, neopentyl glycol, and 1,4-cyclohexanedimethanol.
[0037] Typical examples of polyester include polyethylene terephthalate (PET), polyethylene 2,6-naphthalate (PEN), and polybutylene terephthalate.
[0038] The polyester may be a homopolymer that has not been copolymerized, or a copolyester in which 20 mol% or less of the dicarboxylic acid component is a dicarboxylic acid component other than the main component, and / or 20 mol% or less of the diol component is a diol component other than the main component. In addition, a mixture thereof may be used.
[0039] The polyester can be obtained by a conventionally known method, for example, a method of directly obtaining the polyester by reacting a dicarboxylic acid with a diol, or a method of reacting a lower alkyl ester of a dicarboxylic acid with a diol with a conventionally known transesterification catalyst and then performing a polymerization reaction in the presence of a polymerization catalyst. As the polymerization catalyst, known catalysts such as antimony compounds, germanium compounds, titanium compounds, and aluminum compounds can be used.
[0040] The intrinsic viscosity of the polyester is preferably 0.55 to 0.75 dl / g, and more preferably 0.60 dl / g or more and 0.70 dl / g or less, as measured by the method described in the section of Examples described later.
[0041] (Polymers incompatible with polyester)
[0042] By making the polyester film, especially the polyester resin layer, contain a polymer incompatible with polyester, the polyester film stretched at least in a uniaxial direction can contain countless fine cavities. The polyester film scatters light through the fine cavities, not only making the white color opaque, but also reducing the apparent density of the polyester film. In addition, the image forming material containing thermoplastic resin such as toner printed on the surface of the polyester film can be easily fixed and easily peeled off and removed.
[0043] By including a polymer incompatible with polyester in the surface layer of the polyester film, when it is used as a recording material for copy paper or printing paper, the image forming material containing thermoplastic resin such as the toner printed on the surface of the laminated white polyester film can be easily fixed and can be easily peeled off and removed. That is, by having fine cavities in the surface layer of the polyester film or roughening the surface, the anchoring effect for fixing the image forming material well can be achieved. In addition, by including a polymer incompatible with polyester in the surface layer, it becomes possible to adjust the fixing force of the image forming material, so it can also be easily peeled off and removed. It should be noted that, surprisingly, such an effect can be similarly or more obviously achieved when the functional layer described later is provided on the surface of the polyester film.
[0044] Furthermore, in order to ensure sufficient hiding power and reduce weight, the intermediate layer may contain a polymer incompatible with polyester, if necessary.
[0045] It should be noted that, when the polyester film is a laminated structure, the polymer incompatible with polyester may be contained in all layers of the polyester film, or may be selectively contained in a specific layer. Specifically, the polymer incompatible with polyester is sometimes contained in at least one surface layer of the polyester film, and sometimes in an intermediate layer.
[0046] As the polymer incompatible with polyester, conventionally known polymers can be used, for example, polyolefins, polystyrenes, polyacrylic acids, polycarbonates, etc., among which polyolefins and polystyrenes are preferred, and polyolefins are particularly preferred. Furthermore, among polyolefins, polypropylene, polyethylene, poly-4-methyl-1-pentene, amorphous polyolefins, etc. can be cited, among which, polypropylene is more preferred if the formation of cavities and the ease of film formation are considered.
[0047] In addition, as the polymer incompatible with polyester, a polyester different from the main component resin constituting the polyester film may be used.
[0048] When polypropylene is used as the polymer incompatible with polyester, the content of propylene units in the polypropylene is preferably 80 mol% or more, more preferably 90 mol% or more, and further preferably 95 mol% or more. By reducing the content of copolymer units other than propylene units or using within the above range, the formation of fine cavities can be sufficient.
[0049] In the above-mentioned polyester resin layer, the content ratio of the polymer incompatible with the polyester relative to the polyester is preferably 1 to 70 parts by mass of the polymer incompatible with the polyester relative to 100 parts by mass of the polyester, wherein it is further preferably contained in a ratio of 2 parts by mass or more or 50 parts by mass or less, wherein it is contained in a ratio of 3 parts by mass or more or 40 parts by mass or less, and particularly preferably contained in a ratio of 5 parts by mass or more or 35 parts by mass or less.
[0050] When polypropylene is used as the polymer incompatible with polyester, the melt flow index of polypropylene under the conditions of temperature 230° C. and load 2.16 kg (21.2 N) is generally 0.5 ml / 10 minutes or more, preferably 1 ml / 10 minutes or more, more preferably 3 ml / 10 minutes or more, and further preferably 5 ml / 10 minutes or more as the lower limit. In the above range, a sufficient size of the cavity can be generated, and breakage during stretching can be easily avoided.
[0051] On the other hand, the upper limit is usually 50 ml / 10 minutes or less, preferably 40 ml / 10 minutes or less, more preferably 30 ml / 10 minutes or less, and further preferably 25 ml / 10 minutes or less. In the above range, the jig can be prevented from falling off during transverse stretching, and productivity can be maintained.
[0052] The lower limit of the content of "polymers incompatible with polyester" in the polyester film is usually 1% by weight or more, preferably 2% by weight or more, more preferably 3% by weight or more, further preferably 5% by weight or more, and particularly preferably 8% by weight or more. By using it in the above range, the amount of fine cavities generated in the film becomes sufficient, the hiding power of the film is improved, and the effect of reducing the apparent density, that is, lightweighting, becomes sufficient. In addition, the lubricity of the film and the note-taking properties of pencils, etc. are also improved, which is also beneficial for printing and conveying properties. Furthermore, the text and images produced by the printed image-forming material are easily fixed on the surface of the film, and become easy to peel off and remove, so that the film can be reused as a recorded material for copy paper and printing paper.
[0053] On the other hand, the upper limit of the content of the "polymer incompatible with polyester" in the polyester film is usually 70% by weight or less, preferably 50% by weight or less, more preferably 40% by weight or less, further preferably 35% by weight or less, particularly preferably 30% by weight or less, and most preferably 25% by weight or less. By using the "polymer incompatible with polyester" in a content within this range, the amount of voids generated will not be too large, and there is a tendency to easily suppress breakage during stretching.
[0054] It should be noted that, when the polyester film is a laminated structure, the above content may refer to the average content in all layers of the polyester film, or may refer to the content in a specific layer. Specifically, it may refer to the content in at least one surface layer of the polyester film, or may refer to the content in an intermediate layer.
[0055] In addition, when the polyester film has a structure of three or more layers, the intermediate layer may be mixed with the remaining parts generated during the film production, such as the ends (edges), the ends (edges) of the master roll, and the remaining parts (lower rolls) of the master roll, etc., within the range not impairing the main purpose of the present invention. By including the recycled products, there is an effect of reducing costs and reducing environmental load.
[0056] In addition to the color tone restriction, from the perspective of film forming stability caused by the reduction of intrinsic viscosity, the content of the regenerated product in the intermediate layer is preferably set to 95% by weight or less, more preferably 85% by weight or less, further preferably 70% by weight or less, particularly preferably 60% by weight or less, and most preferably 40% by weight or less relative to the intermediate layer. The lower limit of the content of the regenerated product in the intermediate layer is not limited and may be 0% by weight. From the perspective of cost reduction, it is preferably 1% by weight or more, more preferably 3% by weight or more, and further preferably 5% by weight or more.
[0057] (Metal compound particles)
[0058] The polyester film may contain metal compound particles for the purpose of further improving hiding power and whiteness. When the polyester film has two or more layers, the metal compound particles are preferably also contained in the polyester resin layer.
[0059] When the polyester film has a structure of three or more layers, the layer containing the metal compound particles may be a surface layer or an intermediate layer. In order to effectively improve the hiding power and whiteness, it is preferably contained in the surface layer.
[0060] The metal compound particles tend to complement the white opacity due to the light scattering effect of fine cavities formed by the compounding of the "polymer incompatible with polyester", and thus tend to provide a higher hiding power and whiteness.
[0061] Examples of the metal compound particles include titanium oxide, calcium carbonate, barium sulfate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, zirconium oxide, etc. Among them, from the viewpoint of improving hiding power and whiteness, titanium oxide, calcium carbonate, barium sulfate, etc. are preferred, and titanium oxide is particularly suitable.
[0062] The lower limit of the average particle size of the metal compound particles is usually 0.05 μm or more, preferably 0.10 μm or more, more preferably 0.20 μm or more, and further preferably 0.25 μm or more, and the upper limit is usually 0.50 μm or less, preferably 0.45 μm or less, and more preferably 0.40 μm or less. By using metal compound particles having an average particle size within the above range, the covering rate when forming a film becomes sufficient, and there is a tendency that the back image protrusion is improved when the entire surface is printed on both sides of the film.
[0063] The shape of the above-mentioned compound particles is not particularly limited, and can be spherical, blocky, rod-shaped, flat, etc. In addition, there is no particular restriction on its hardness, specific gravity, color, etc. These particles can be used in combination of two or more as needed.
[0064] The lower limit of the content of the metal compound particles is preferably 1% by weight or more, more preferably 2% by weight or more, and further preferably 3% by weight or more, and the upper limit is usually 30% by weight or less, preferably 20% by weight or less, more preferably 15% by weight or less, further preferably 13% by weight or less, and particularly preferably 10% by weight or less. By making the content of the metal compound particles within the above range, sufficient hiding power can be given, and it is also cost-effective, and there is a tendency to become the best use as a recording material for copy paper and printing paper instead of paper made of paper.
[0065] It should be noted that, when the polyester film is a laminated structure, the above content may refer to the average content in all layers of the polyester film, or may refer to the content in a specific layer. Specifically, it may refer to the content in at least one surface layer of the polyester film, or may refer to the content in an intermediate layer.
[0066] (Particles other than metal compound particles)
[0067] In order to improve the handling property and lubricity of the laminated white film 1, the polyester film may contain particles other than the metal compound particles exemplified above.
[0068] As particles other than the metal compound particles exemplified above, specifically, silica particles and organic particles can be cited. As organic particles, specifically, acrylic resins, styrene resins, urea resins, phenolic resins, epoxy resins, benzoguanamine resins, etc. can be cited. Among them, silica particles are particularly preferred in terms of exerting effects in a small amount.
[0069] The average particle size of particles (silicon dioxide particles or organic particles) other than the metal compound particles exemplified above is preferably more than 0.50 μm, more preferably more than 1.0 μm, further preferably more than 1.5 μm, and particularly preferably more than 2.0 μm. By making the average particle size of particles other than metal compound particles the above range, there is a tendency to impart sufficient slipperiness. In addition, the upper limit of the average particle size of the particles is usually less than 15.0 μm, preferably less than 12.0 μm, more preferably less than 10.0 μm, and further preferably less than 8.0 μm. By setting the above range, the surface of the film will not become excessively rough, and it is easy to peel off and remove the text and images such as the image forming material printed on the surface of the film, and there is a tendency to reuse the film as a recorded material for copy paper and printing paper. Furthermore, there is no need to extremely thicken the thickness of the surface layer from the surface where the particles fall off, and the optimal range of thickness is also wide, so it becomes a preferred method.
[0070] The shape of the particles (silicon dioxide particles or organic particles) other than the metal compound particles exemplified above is not particularly limited, and may be spherical, blocky, rod-shaped, flat, etc. In addition, there is no particular limitation on its hardness, specific gravity, color, etc. These particles may be used in combination of two or more as needed.
[0071] The content of particles (silicon dioxide particles or organic particles) other than the metal compound particles exemplified above also depends on the average particle size, so it cannot be generalized. For example, relative to a polyester film containing silicon dioxide particles or organic particles, it is usually less than 5% by weight, preferably less than 3% by weight, more preferably less than 2% by weight, and further preferably less than 1% by weight, and the lower limit of the preferred range is more than 0.005% by weight, more preferably more than 0.05% by weight, and further preferably more than 0.1% by weight. If it is within this range, the surface roughness of the film can be moderate, and there is a tendency to achieve the goal of slipperiness. In addition, not only slipperiness is imparted, but also the text and images such as the image forming material printed on the surface of the film are easily peeled off and removed, and there is a tendency to repeat the film as a recording material for copy paper and printing paper, which can become the best. Furthermore, as the role of silicon dioxide particles and organic particles, there is a tendency to further improve the writing properties of pencils, mechanical pencils, ballpoint pens, etc.
[0072] It should be noted that, when the polyester film is a laminated structure, the above content may refer to the average content in all layers of the polyester film, or may refer to the content in a specific layer. Specifically, it may refer to the content in at least one surface layer of the polyester film, or may refer to the content in an intermediate layer.
[0073] (Other ingredients)
[0074] The polyester film as the base material of the laminated white film 1 contains an incompatible polymer, so the extruded sheet is stretched at least along a uniaxial direction to obtain a fine independent space (cavity) inside the film. Thus, in order to further refine the cavity or increase the hiding power and whiteness, for example, a surfactant, inactive particles, a fluorescent whitening agent, etc. can be mixed.
[0075] In addition to the above-mentioned particles and polymers incompatible with polyester, the polyester film may contain conventionally known antioxidants, heat stabilizers, lubricants, antistatic agents, dyes, pigments, etc. as needed. In addition, it may contain ultraviolet absorbers, particularly benzoxazinone ultraviolet absorbers, etc., depending on the application.
[0076] (Layered structure)
[0077] When the polyester film as the base material of the laminated white film 1 has a laminated structure of two or more layers, it is preferred that if it is two layers, any one of the layers is the above-mentioned polyester resin layer, and if it is three or more layers, the surface layer thereof is the above-mentioned polyester resin layer.
[0078] For example, in the case of a laminated structure of three or more layers, if the surface layer contains the above-mentioned polyester and a polymer incompatible with the polyester, fine cavities can be set by stretching, thereby achieving light weight, hiding power and whiteness. In addition, the surface roughness can be adjusted, so the writing property can be improved, and the image produced by the image forming material can be easily fixed and can be peeled off after use.
[0079] If the surface layer further contains metal compound particles, the hiding power and whiteness can be further improved, and if particles other than the metal compound particles are further contained, the lubricity can be improved.
[0080] On the other hand, if the intermediate layer other than the surface layer contains the above-mentioned polyester, it may contain a polymer incompatible with the polyester, metal compound particles, and particles other than the metal compound particles as required. From the viewpoint of reducing costs and reducing environmental loads, it is preferred to reduce the content of the metal compound particles and particles other than the metal compound particles as small as possible, and to use polyester as a recycled product.
[0081] (thickness)
[0082] The thickness of the polyester film is preferably 10 μm to 1000 μm, more preferably 20 μm or more and 500 μm or less, more preferably 30 μm or more and 400 μm or less, and more preferably 38 μm or more and 350 μm or less.
[0083] By using the above-mentioned range, the hardness (rigidity) and handleability of the film can be made sufficient, and clogging of the film during the conveying process in the copying machine can be reduced.
[0084] When the polyester film is a laminated structure of more than three layers as described above, the thickness of each surface layer is preferably 1 μm to 50 μm, wherein more preferably 2 μm or more or 40 μm or less, wherein more preferably 3 μm or more or 30 μm or less, wherein more preferably 4 μm or more or 25 μm or less. By using it in the above range, the performance of the above-mentioned metal compound particles and particles other than the metal compound particles can be fully utilized, and the manufacturing cost can also be suppressed to be cheap.
[0085] (Apparent density)
[0086] The lower limit of the apparent density of polyester film is 0.7 g / cm 3 Above, preferably 0.75g / cm 3 More preferably 0.8 g / cm 3By setting the lower limit of the apparent density to the above range, the strength of the film can be maintained, and when the film is used as a recording material instead of information printing medium, i.e., copy paper or printing paper, the clogging of the film during the conveying process in the copier can be reduced, so that optimal printing can be performed.
[0087] On the other hand, the upper limit of the apparent density is 1.3 g / cm 3 Below, preferably 1.2g / cm 3 Below, more preferably 1.1 g / cm 3 By setting the upper limit of the apparent density to the above range, the workload when conveying a large amount of printed matter can be reduced, and the reduction of CO2 generated during the conveyance of the film (sheet) can be reduced to reduce the environmental load and reduce costs.
[0088] The apparent density of the polyester film can be adjusted by mixing an incompatible polymer lighter than the main component resin, ie, polyester, and stretching the film in at least one axial direction to form fine independent cavities inside the film. However, the method is not limited to these.
[0089] (Physical properties of polyester film)
[0090] The surface arithmetic mean roughness (Ra) of the polyester film is in accordance with JIS B0601 (2001). The arithmetic mean roughness (Ra) varies depending on the intended use, and the upper limit is usually 950 nm or less, preferably 850 nm or less, and more preferably 800 nm or less. By using a polyester film having an arithmetic mean roughness (Ra) in the above range, the text and image formed on the surface of the film, such as an image forming material containing a thermoplastic resin, are easily fixed and can be easily peeled off and removed, and there is a tendency that the film can be repeatedly used as a recording material for copy paper and printing paper.
[0091] On the other hand, the lower limit of the arithmetic mean roughness (Ra) is usually 100 nm or more, preferably 200 nm or more, more preferably 300 nm or more, and further preferably 350 nm or more. By setting the arithmetic mean roughness (Ra) to the above range, the covering property and the conveying property can be made sufficient, and there is a tendency to form a film that is optimal for recording materials such as copy paper and printing paper. There is also a tendency to have sufficient writing properties.
[0092] The b value (reflection method) indicating the yellow hue of the polyester film is usually below 0, preferably below -0.20, more preferably below -0.40, further preferably below -0.50, particularly preferably below -0.60, and the lower limit is not particularly limited, preferably above -5.0. By using it in the above range, the yellow hue is suppressed and the whiteness can be made good. Furthermore, when used as a recording material for color printing, there is a tendency to make the resulting image quality excellent.
[0093] The polyester film has a heat shrinkage rate in the film longitudinal direction (MD) and the film transverse direction (TD) at 150° C. for 30 minutes of usually 2.8% or less, preferably 2.3% or less, more preferably 2.0% or less in absolute value.
[0094] By setting the heat shrinkage rate of the polyester film to the above range, it is possible to prevent the dimensional stability of the film from being damaged due to the influence of heat when printing on the recording material by electronic photography, thermal transfer, etc. In particular, the edge of the film (sheet), that is, the part where wrinkles are easily generated, can also suppress the occurrence of wrinkles in the polyester film, and there is a tendency to suppress the phenomenon of distortion and unevenness in text and images and the reduction of image quality. In addition, once wrinkles occur, they cannot disappear, and it becomes impossible to reuse them as a recording material for copy paper or printing paper. Therefore, it is preferred to avoid wrinkles as much as possible.
[0095] The hiding power (OD) of the polyester film is measured by a Macbeth densitometer for a single film and is usually 0.30 or more, preferably 0.35 or more, more preferably 0.40 or more, and further preferably 0.45 or more. By using the above range, the protrusion of the back image when printing on both sides of the film can be reduced, and there is a tendency to obtain good quality text and images. On the other hand, the upper limit of the hiding power (OD) is not particularly limited. If the balance of other physical properties is considered, it is preferably 1 or less, and more preferably 0.9 or less.
[0096] The whiteness of the polyester film is measured by a colorimeter to measure the Hunter whiteness (Wb) of a single film, and the lower limit is usually 80.0% or more, preferably 81.0% or more, more preferably 82.0% or more, further preferably 83.0% or more, and particularly preferably 83.5% or more. By making the whiteness within the above range, when the recorded material is used as an information printing medium, i.e., copy paper, printing paper, etc. instead of paper, especially when color printing is performed, the text and image become high-definition and tend to be preferred in quality. In addition, it also depends on the purpose of use. In order to reflect the sense of luxury, it is preferably higher, and in particular, the upper limit is not limited. On the other hand, when used for purposes that pay attention to gloss, the upper limit of the preferred range is 95.0% or less.
[0097] <Functional layer>
[0098] Next, the functional layers constituting the laminated white film 1 will be described.
[0099] The functional layer can function as a recorded layer on which the image forming material is directly attached. The recorded layer in the present invention is a layer that not only fixes the attached image forming material but also removes the image forming material together with the resin layer when the resin layer described later is set.
[0100] The functional layer in the laminated white film 1 preferably has antistatic properties and mold release properties.
[0101] In order to reduce the apparent density, whiten the film without cost, and easily peel off the printed text and images such as image-forming materials containing thermoplastic resin, the laminated white film 1 preferably has a polyester resin layer containing polyester and a polymer incompatible with polyester, and more preferably has the polyester resin layer on the surface. However, when a functional layer is provided, it is judged that it is sometimes difficult to achieve the performance of easily peeling off the text and images such as image-forming materials on the surface, so it is preferred that the functional layer also has a demolding performance.
[0102] (Antistatic Agent)
[0103] The laminated white film 1 preferably has a functional layer containing an antistatic agent on at least one side for the purpose of preventing overlapping feeding during paper transportation in a copier or multifunction machine when used as a recording material for copy paper or printing paper, and preventing adhesion of paper sheets during paper handling. In addition, by containing an antistatic agent in the functional layer, there is no clogging of the film in the multifunction machine, and overlapping feeding of the printed film does not occur, and the printed film can be transported independently one by one, and dust adhesion can be prevented, so that a film of good quality and a film printed product with good image quality can be formed.
[0104] The antistatic agent contained in the functional layer is not particularly limited, and a conventionally known antistatic agent can be used. For example, a polymer antistatic agent is preferred from the viewpoint of good heat resistance and moisture-heat resistance.
[0105] Examples of the polymer antistatic agent include compounds having an ammonium group, polyether compounds, compounds having a sulfonic acid group, betaine compounds, and conductive polymers.
[0106] Considering the antistatic performance, the compounds having an ammonium group and the compounds having a sulfonic acid group are preferred. Considering the compatibility with other materials forming the functional layer such as a release agent, the compounds having an ammonium group are more preferred. In addition, conductive polymers are preferred because of their excellent antistatic properties. However, there is a possibility that the materials are expensive and their use is limited in applications that are extremely averse to coloring.
[0107] Examples of the compound having an ammonium group include ammonium compounds of aliphatic amines, alicyclic amines, and aromatic amines.
[0108] The compound with ammonium group is preferably a macromolecular compound with ammonium group, and the ammonium group is not used as a counter ion, but is preferably a structure incorporated into the main chain and the side chain of the macromolecular. For example, the structure of a polymer formed by polymerizing a monomer containing a precursor of an ammonium group such as an addition-polymerizable ammonium group or an amine can be enumerated, which is suitable for use. As a polymer, the monomer containing a precursor of an ammonium group such as an addition-polymerizable ammonium group or an amine can be polymerized alone, or it can be a copolymer of a monomer containing them and other monomers.
[0109] Among the compounds having an ammonium group, compounds having a pyrrolidinium ring are also preferred in terms of excellent antistatic properties and heat resistance stability.
[0110] The two substituents bonded to the nitrogen atom of the compound having a pyrrolidinium ring are each independently an alkyl group, a phenyl group, or the like, and these alkyl groups and phenyl groups may be substituted with the groups shown below.
[0111] The substitutable groups include, for example, hydroxyl, amide, ester, alkoxy, phenoxy, naphthoxy, thioalkoxy, thiophenoxy, cycloalkyl, trialkylammoniumalkyl, cyano, and halogen. In addition, the two substituents bonded to the nitrogen atom may be chemically bonded, for example, -(CH2) m -(m=an integer from 2 to 5), -CH(CH3)CH(CH3)-, -CH=CH-CH=CH-, -CH=CH-CH=N-, -CH=CH-N=CH-, -CH2OCH2-, -(CH2)2O(CH2)2-, etc.
[0112] The polymer having a pyrrolidinium ring can be obtained by cyclopolymerizing a diallylamine derivative using a free radical polymerization catalyst. The polymerization can be carried out by using a polymerization initiator such as hydrogen peroxide, benzoyl peroxide, tert-butyl peroxide, etc. in a polar solvent such as water or methanol, ethanol, isopropanol, formamide, dimethylformamide, dioxane, acetonitrile, etc. as a solvent, by a known method, but is not limited to these. In the present invention, a diallylamine derivative and a compound having a polymerizable carbon-carbon unsaturated bond can be used as a copolymerization component.
[0113] In addition, as a compound having an ammonium group, the antistatic agent is preferably a polymer having a structure of the following formula (1) in terms of excellent antistatic properties and moisture-heat resistance stability. A homopolymer or copolymer having a structure of the following formula (1) may be copolymerized with other plural components.
[0114]
[0115] For example, in the above formula, the substituent R 1 is a hydrogen atom or a hydrocarbon group such as an alkyl group or a phenyl group having 1 to 20 carbon atoms, R 2 is -O-, -NH- or -S-, R 3 is an alkylene group having 1 to 20 carbon atoms or other structures that can form the structure of Formula 1, R 4 , R 5 , R 6 Each of them is independently a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, a hydrocarbon group such as a phenyl group, or a hydrocarbon group having a functional group such as a hydroxyalkyl group, - For various counter ions.
[0116] Among the above, in particular, from the viewpoint of excellent antistatic properties and moisture-heat resistance stability, in formula (1), the substituent R 1 Preferably, a hydrogen atom or an alkyl group having 1 to 6 carbon atoms is 3 Preferably, the alkyl group has 1 to 6 carbon atoms, and R 4 , R 5 , R 6 Preferably, each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and more preferably, R 4 , R 5 , R 6 Any one of the substituents is a hydrogen atom, and the other substituent is an alkyl group having 1 to 4 carbon atoms.
[0117] Examples of anions that serve as counter ions (counter ions) of the ammonium group of the compound having an ammonium group include ions such as halogen ions, sulfonate ions, sulfate ions, phosphate ions, nitrate ions, and carboxylate ions.
[0118] The number average molecular weight of the compound having an ammonium group is usually 1,000 to 500,000, preferably 2,000 to 350,000, and more preferably 5,000 to 200,000. When the molecular weight is less than 1,000, the strength of the functional layer may be weakened, and the heat resistance stability may be poor. When the molecular weight exceeds 500,000, the viscosity of the coating liquid may be increased, and the handling and coating properties may be deteriorated.
[0119] Examples of the polyether compound include polyethylene oxide, polyether ester amide, and acrylic resins having polyethylene glycol in a side chain.
[0120] The compound having a sulfonic acid group refers to a compound containing sulfonic acid or a sulfonate in the molecule, and for example, a compound containing a large amount of sulfonic acid or a sulfonate such as polystyrenesulfonic acid is preferably used.
[0121] As the conductive polymer, for example, polythiophene, polyaniline, polypyrrole, polyacetylene, etc. can be cited, among which, for example, polythiophene such as poly(3,4-ethylenedioxythiophene) and polystyrene sulfonic acid are preferably used. In terms of lowering the resistance value, conductive polymers are more suitable than the above-mentioned other antistatic agents. However, on the other hand, in the use of coloring and cost, there is no need to reduce the amount of use.
[0122] The lower limit of the content of the antistatic agent in the functional layer is usually 1% by weight or more, preferably 3% by weight or more, more preferably 5% by weight or more, further preferably 10% by weight or more, and particularly preferably 20% by weight or more. Moreover, the upper limit is usually 80% by weight or less, preferably 70% by weight or less, more preferably 60% by weight or less, further preferably 55% by weight or less, and particularly preferably 50% by weight or less. By using the antistatic agent in the above range, sufficient antistatic property can be obtained, which is effective in preventing the adhesion of films to each other and preventing the adhesion of dust, and there is a tendency for printing and conveying properties and image quality to become excellent.
[0123] (Release Agent)
[0124] It is preferred that the functional layer be provided with a releasable property so that the image forming material containing a thermoplastic resin formed on the surface of the film can be suitably peeled off and removed after printing.
[0125] The functional layer with demoulding performance may be the same as or different from the functional layer containing the antistatic agent. In particular, for reasons described later, it is preferred that the functional layer containing the antistatic agent has demoulding performance. It should be noted that when the functional layer with demoulding performance and the functional layer containing the antistatic agent are different layers, it is preferred that the functional layer with demoulding performance is the outer layer.
[0126] It was found that by giving the functional layer a demoulding property, the function of peeling and removing the image forming material can be more appropriately realized. That is, it was found that a method can realize the opposite characteristics of fixing property and peeling property in one functional layer to a higher degree. Considering that the peeling property cannot be realized in the conventional functional layer with fixing property, and on the other hand, the fixing property cannot be realized in the conventional functional layer with peeling property, it can be said that this technology is a technology with a very high effect. In addition, even if the functional layer with fixing property and the functional layer with peeling property are stacked, it is difficult to reflect any performance, and the performance of the functional layer in the outermost layer is mainly reflected.
[0127] In order to impart release properties to the image forming material or the like, the functional layer preferably contains a release agent.
[0128] There are no particular restrictions on the release agent, and conventionally known release agents can be used, for example, compounds containing long-chain alkyl groups, fluorine compounds, organosilicon compounds, waxes, etc. can be cited. Among them, from the aspect of less pollution and excellent stripping and removal of image-forming substances, long-chain alkyl compounds and fluorine compounds are preferred, and long-chain alkyl compounds are more preferred. In addition, when it is desired to attach importance to the stripping and removal of image-forming substances, organosilicon compounds are particularly preferred. In addition, when it is desired to attach importance to the printability of the image-forming substance on the surface, wax is effective. These release agents can be used alone or in combination.
[0129] When the functional layer is provided by coating, from the viewpoint of wettability to the polyester film, a compound containing a long-chain alkyl group is preferred among the release agents.
[0130] The long-chain alkyl group-containing compound refers to a compound having a linear or branched alkyl group having usually 6 or more, preferably 8 or more, and more preferably 12 or more carbon atoms.
[0131] Examples of the alkyl group include a hexyl group, an octyl group, a decyl group, a lauryl group, an octadecyl group, and a behenyl group.
[0132] Compounds having an alkyl group include, for example, various polymer compounds containing long-chain alkyl groups, amine compounds containing long-chain alkyl groups, ether compounds containing long-chain alkyl groups, quaternary ammonium salts containing long-chain alkyl groups, etc. Considering heat resistance and contamination, polymer compounds are preferred. In addition, from the viewpoint of effectively obtaining mold release properties, polymer compounds having long-chain alkyl groups in side chains are more preferred.
[0133] A polymer compound having a long-chain alkyl group in a side chain can be obtained by reacting a polymer having a reactive group with a compound having an alkyl group that can react with the reactive group. Examples of the reactive group include hydroxyl, amino, carboxyl, and acid anhydride. Examples of compounds having these reactive groups include polyvinyl alcohol, polyethyleneimine, polyvinylamine, polyester resins containing reactive groups, and poly(meth)acrylic resins containing reactive groups. Among these, polyvinyl alcohol is preferred in view of demoulding properties and ease of operation.
[0134] Examples of the compound having an alkyl group that can react with the above-mentioned reactive group include isocyanates containing long-chain alkyl groups such as hexyl isocyanate, octyl isocyanate, decyl isocyanate, lauryl isocyanate, octadecyl isocyanate, and behenyl isocyanate; acid chlorides containing long-chain alkyl groups such as hexyl chloride, octyl chloride, decyl chloride, lauryl chloride, octadecyl chloride, and behenyl chloride; amines containing long-chain alkyl groups; alcohols containing long-chain alkyl groups, etc. Among them, isocyanates containing long-chain alkyl groups are preferred, and octadecyl isocyanate is particularly preferred, in view of mold release properties and ease of handling.
[0135] In addition, the polymer compound having a long-chain alkyl group in the side chain can be obtained by a polymer of a long-chain alkyl (meth)acrylate or a copolymer of a long-chain alkyl (meth)acrylate and other vinyl-containing monomers. Examples of the long-chain alkyl (meth)acrylate include hexyl (meth)acrylate, octyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, octadecyl (meth)acrylate, and behenyl (meth)acrylate.
[0136] Fluorine compounds refer to compounds containing fluorine atoms in the compound. In order to reduce the contamination, polymers containing fluorine atoms are preferred. In terms of the coating appearance using online coating, organic fluorine compounds are suitable, for example, compounds containing fluorine alkyl groups such as perfluoroalkyl groups, polymers of olefin compounds containing fluorine atoms, aromatic fluorine compounds such as fluorobenzene, etc. can be cited. From the viewpoint of demolding properties, fluorine alkyl-containing compounds are preferred, among which perfluoroalkyl-containing compounds are preferred. Compounds containing long-chain alkyl compounds as described later in further fluorine compounds can also be used.
[0137] As a compound containing a perfluoroalkyl group, for example, perfluoroalkyl (meth) acrylate, perfluoroalkyl methyl (meth) acrylate, 2-perfluoroalkyl ethyl (meth) acrylate, 3-perfluoroalkyl propyl (meth) acrylate, 3-perfluoroalkyl-1-methylpropyl (meth) acrylate, 3-perfluoroalkyl-2-propylene (meth) acrylate and other perfluoroalkyl-containing (meth) acrylates, polymers thereof; perfluoroalkyl methyl vinyl ether, 2-perfluoroalkyl ethyl vinyl ether, 3-perfluoropropyl vinyl ether, 3-perfluoroalkyl-1-methylpropyl vinyl ether, 3-perfluoroalkyl-2-propylene vinyl ether and other perfluoroalkyl-containing vinyl ethers, polymers thereof, etc. If heat resistance and contamination are considered, polymers are preferred. The polymer may be only a single compound or a polymer of multiple compounds.
[0138] In addition, from the viewpoint of mold release properties, the number of carbon atoms of the perfluoroalkyl group is preferably 3 to 11. It may be a polymer with a compound containing a long-chain alkyl compound as described below. In addition, from the viewpoint of adhesion to a substrate, a polymer with vinyl chloride is also preferred.
[0139] As the organosilicon compound, for example, alkyl organosilicon such as dimethyl organosilicon and diethyl organosilicon, and phenyl organosilicon having phenyl group, methylphenyl organosilicon, etc. can be mentioned. Organosilicon having various functional groups can also be used, for example, ether group, hydroxyl group, amino group, epoxy group, carboxylic acid group, halogen group such as fluorine, perfluoroalkyl group, etc. As other functional groups, organosilicon having vinyl group and hydrogen organosilicon having hydrogen atom directly bonded to silicon atom are also common, and the two can also be used in combination as addition type (type utilizing addition reaction of vinyl group and hydrogen silane) organosilicon.
[0140] In addition, as the organosilicon compound, modified silicones such as acrylic grafted silicone, silicone grafted acrylic, amino modified silicone, and perfluoroalkyl modified silicone can also be used. If heat resistance and pollution resistance are taken into consideration, it is preferred to use a curable silicone resin, and as the type of curable type, any curing reaction type such as condensation type, addition type, and active energy ray curing type can be used.
[0141] The wax is a wax selected from natural waxes, synthetic waxes, and waxes blended with these.
[0142] Natural wax refers to plant wax, animal wax, mineral wax, and petroleum wax. Examples of plant wax include candelilla wax, carnauba wax, rice bran wax, wood wax, and jojoba oil. Examples of animal wax include beeswax, lanolin, and spermaceti. Examples of mineral wax include montan wax, ozokerite, and white ceresin. Examples of petroleum wax include paraffin wax, microcrystalline wax, and vaseline.
[0143] Examples of the synthetic wax include synthetic hydrocarbons, modified waxes, hydrogenated waxes, higher fatty acid esters, fatty acid amides, amines, imides, ester waxes, and ketones.
[0144] As synthetic hydrocarbons, specifically, there can be mentioned Fischer-Tropsch wax (also known as Sasol wax) and polyethylene wax. In addition, there can be mentioned low molecular weight polymers (specifically, polymers with a number average molecular weight of 500 to 20,000), namely, the following polymers, namely, polypropylene, ethylene-acrylic acid copolymer, polyethylene glycol, polypropylene glycol, blocks or grafted combinations of polyethylene glycol and polypropylene glycol, etc.
[0145] Specific examples of the modified wax include montan wax derivatives, paraffin wax derivatives, microcrystalline wax derivatives, etc. The derivatives herein refer to compounds obtained by any treatment of purification, oxidation, esterification, saponification, or a combination thereof.
[0146] Moreover, as a hydrogenated wax, hydrogenated castor oil and a hydrogenated castor oil derivative are mentioned specifically,.
[0147] Among them, from the viewpoint of stability of properties such as blocking, synthetic wax is preferred as the release agent in the functional layer, and polyethylene wax is more preferred, and oxidized polyethylene wax is further preferred. The number average molecular weight of the synthetic wax is usually 500 to 30,000, preferably 1,000 to 15,000, and more preferably 2,000 to 8,000, from the viewpoint of stability of properties such as blocking and handling properties.
[0148] The lower limit of the content of the release agent in the functional layer is usually 0% by weight or more, preferably 3% by weight or more, more preferably 5% by weight or more, further preferably 8% by weight or more, and particularly preferably 10% by weight or more. Moreover, the upper limit is usually 80% by weight or less, preferably 70% by weight or less, more preferably 60% by weight or less, further preferably 50% by weight or less, and particularly preferably 40% by weight or less. By using the release agent in the above range, there is a tendency to ensure fixability with image forming materials, etc., and to improve peelability and to easily peel off and remove image forming materials.
[0149] (polymer)
[0150] In order to improve the fixability of image forming materials to the functional layer, improve the ease of forming the functional layer, or the wettability of the substrate film when the functional layer is set by coating, the functional layer preferably contains a polymer (a polymer other than the above-mentioned antistatic agent, release agent, and cross-linking agent described later).
[0151] As the polymer used in the functional layer, a polymer known in the past can be used. As a specific example of the polymer, acrylic resin, polyurethane resin, polyester resin, polyethylene (polyvinyl alcohol, vinyl chloride-vinyl acetate copolymer, etc.), polyalkylene glycol, polyalkylene imine, methylcellulose, hydroxy cellulose, starch, etc. can be cited. Among them, from the viewpoint of improving the appearance, the adhesion with the substrate film, antistatic performance, and the stabilization of the demoulding performance, acrylic resin, polyurethane resin, polyester resin, polyvinyl alcohol are preferred, acrylic resin, polyurethane resin, polyester resin are more preferred, and acrylic resin, polyurethane resin are further preferred. In addition, from the viewpoint of the stability of the coating liquid in the state when the antistatic performance, demoulding performance are stabilized or the functional layer is formed by coating, acrylic resin and polyvinyl alcohol are preferred. If comprehensive performance is considered, acrylic resin or polyurethane resin are preferred, and acrylic resin is particularly preferred.
[0152] The acrylic resin as the above-mentioned polymer contained in the functional layer refers to a polymer formed by a polymerizable monomer including an acrylic acid-based monomer and a methacrylic acid-based monomer. They can be homopolymers or copolymers, and copolymers with polymerizable monomers other than acrylic acid-based monomers and methacrylic acid-based monomers. In addition, copolymers of these polymers with other polymers (such as polyesters, polyurethanes, etc.) are also included. For example, block copolymers and graft copolymers. Or it also includes: polymers obtained by polymerizing polymerizable monomers in a polyester solution or a polyester dispersion (a mixture of polymers depending on the situation). Similarly, it also includes: polymers obtained by polymerizing polymerizable monomers in a polyurethane solution or a polyurethane dispersion (a mixture of polymers depending on the situation). Similarly, it also includes: polymers obtained by polymerizing polymerizable monomers in other polymer solutions or dispersions (a mixture of polymers depending on the situation). In addition, in order to further improve the adhesion, hydroxyl groups and amino groups may also be contained.
[0153] The polymerizable monomer is not particularly limited, and examples thereof include various carboxyl-containing monomers such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid, fumaric acid, maleic acid, and citraconic acid, and salts thereof; various hydroxyl-containing monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, monobutyl hydroxyfumarate, and monobutyl hydroxyitaconate; methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, and lauryl (meth)acrylate; various (meth)acrylates; various nitrogen-containing compounds such as (meth)acrylamide, diacetone acrylamide, N-hydroxymethyl acrylamide or (meth)acrylonitrile; various styrene derivatives such as styrene, α-methylstyrene, divinylbenzene, and vinyltoluene; various vinyl esters such as vinyl propionate; various silicon-containing polymerizable monomers such as γ-methacryloxypropyltrimethoxysilane and vinyltrimethoxysilane; phosphorus-containing vinyl monomers; various halogenated vinyls such as vinyl chloride and vinylidene chloride; various conjugated dienes such as butadiene.
[0154] The polyurethane resin as the above-mentioned polymer contained in the functional layer refers to a high molecular compound having a carbamate bond in the molecule, which is usually prepared by the reaction of a polyol and an isocyanate. As the polyol, polyester polyols, polycarbonate polyols, polyether polyols, polyolefin polyols, and acrylic polyols can be cited, and these compounds can be used alone or in combination.
[0155] Examples of the polyester polyols include polyesters prepared from polycarboxylic acids (malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, fumaric acid, maleic acid, terephthalic acid, isophthalic acid, etc.) or their anhydrides and polyols (ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 2-methyl-2,4-pentanediol, 2-methyl-2, Polyester polyols obtained by the reaction of 1,2-propyl-1,3-propanediol, 1,8-octanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2,5-dimethyl-2,5-hexanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-butyl-2-hexyl-1,3-propanediol, cyclohexanediol, bishydroxymethylcyclohexane, dimethanolbenzene, bishydroxyethoxybenzene, alkyldialkanolamine, lactone diol, etc.; polyester polyols having derivative units of lactone compounds such as polycaprolactone; etc.
[0156] The polycarbonate polyols are obtained by dealcoholization reaction of polyols and carbonate compounds. Examples of the polyols include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, and 3,3-dihydroxymethylheptane. Examples of carbonate compounds include dimethyl carbonate, diethyl carbonate, diphenyl carbonate, and ethylene carbonate. Examples of polycarbonate polyols obtained by the reaction of these compounds include poly(1,6-hexamethylene) carbonate and poly(3-methyl-1,5-pentamethylene) carbonate.
[0157] Examples of the polyether polyols include polyethylene glycol, polypropylene glycol, polyethylene propylene glycol, polytetramethylene ether glycol, and polyhexamethylene ether glycol.
[0158] Among the above-mentioned polyols, polyester polyols and polycarbonate polyols are more preferred in consideration of compatibility with other components of the functional layer, antistatic performance, stabilization of mold release performance, and the like.
[0159] As the polyisocyanate compound used to obtain the polyurethane resin, there can be exemplified aromatic diisocyanates such as toluene diisocyanate, xylylene diisocyanate, methylene diphenyl diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, and toluidine diisocyanate, aliphatic diisocyanates having an aromatic ring such as α,α,α',α'-tetramethylxylylene diisocyanate, methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate, alicyclic diisocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and isopropylidene dicyclohexyl diisocyanate, etc. These can be used alone or in combination of a plurality of them.
[0160] A chain extender may be used when synthesizing the polyurethane resin. The chain extender is not particularly limited as long as it has two or more active groups that react with isocyanate groups. Generally, a chain extender having two hydroxyl groups or amino groups is mainly used.
[0161] Examples of the chain extender having two hydroxyl groups include diols such as aliphatic diols such as ethylene glycol, propylene glycol, and butanediol, aromatic diols such as benzyl alcohol and bishydroxyethoxybenzene, and ester diols such as neopentyl glycol hydroxypivalate. Examples of the chain extender having two amino groups include aromatic diamines such as toluenediamine, xylylenediamine, and diphenylmethanediamine; aliphatic diamines such as 2,2-dimethyl-1,3-propylenediamine, 2-methyl-1,5-pentanediamine, trimethylhexanediamine, 2-butyl-2-ethyl-1,5-pentanediamine, 1,8-octanediamine, 1,9-nonanediamine, and 1,10-decanediamine; and alicyclic diamines such as 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane, dicyclohexylmethanediamine, isopropylidenecyclohexyl-4,4′-diamine, 1,4-diaminocyclohexane, and 1,3-bisaminomethylcyclohexane.
[0162] The polyurethane resin may be prepared using a solvent as a medium, preferably water as a medium.
[0163] When dispersing or dissolving the polyurethane resin in water, there are forced emulsification types using an emulsifier, self-emulsification types or water-soluble types in which a hydrophilic group is introduced into the polyurethane resin, etc. In particular, the self-emulsification type in which an ionic group is introduced into the structure of the polyurethane resin to form an ionomer is preferred because it is excellent in storage stability of the liquid, water resistance and transparency of the obtained functional layer.
[0164] At this time, various groups such as carboxyl, sulfonic acid, phosphoric acid, phosphonic acid, and quaternary ammonium salts can be cited as the ionic groups to be introduced. As a method for introducing carboxyl groups into the polyurethane resin, various methods can be adopted in various stages of the polymerization reaction. For example, there are methods in which a resin having a carboxyl group is used as a copolymer component when synthesizing a prepolymer; methods in which a component having a carboxyl group is used as one of the components of a polyol, a polyisocyanate, a chain extender, etc. Particularly preferred is a method in which a carboxyl-containing diol is used to introduce a desired amount of carboxyl groups according to the amount of the component added.
[0165] For example, diols used in the polymerization of polyurethane resins can be copolymerized with dimethylol propionic acid, dimethylol butyric acid, bis-(2-hydroxyethyl) propionic acid, bis-(2-hydroxyethyl) butyric acid, etc. Moreover, it is preferred to form a salt form in which the carboxyl group is neutralized with ammonia, amines, alkali metals, inorganic bases, etc. Particularly preferred are ammonia, trimethylamine, and triethylamine. The above-mentioned polyurethane resin can use the carboxyl group that has left the neutralizer in the drying process after coating as a crosslinking reaction site based on other crosslinking agents. Thus, on the basis of the excellent stability in the liquid state before coating, the durability, solvent resistance, water resistance, adhesion resistance, etc. of the obtained functional layer can be further improved.
[0166] The polyester resin as the polymer contained in the functional layer refers to a polyester resin formed of, for example, the following polycarboxylic acids and polyhydroxy compounds as main components. That is, as the polycarboxylic acid, terephthalic acid, isophthalic acid, phthalic acid, phthalic acid, 4,4'-diphenyl dicarboxylic acid, 2,5-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, 1,4-cyclohexane dicarboxylic acid, terephthalic acid-2-sulfonic potassium, isophthalic acid-5-sulfonic sodium, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, glutaric acid, succinic acid, trimellitic acid, trimesic acid, pyromellitic acid, trimellitic anhydride, phthalic anhydride, p-hydroxybenzoic acid, trimellitic acid monopotassium salt and their ester-forming derivatives, etc. As polyhydroxy compounds, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,6-hexanediol, 2-methyl-1,5-pentanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, terephthalic acid, bisphenol A-ethylene glycol adduct, diethylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polytetrahydrofuran diol, dimethylolpropionic acid, glycerol, trimethylolpropane, sodium dimethylolethylsulfonate, potassium dimethylolpropionate, etc. can be used. One or more of these compounds can be appropriately selected and synthesized into a polyester resin by a conventional polycondensation reaction.
[0167] The polyvinyl alcohol as the above-mentioned polymer contained in the functional layer refers to a substance having a polyvinyl alcohol portion, and for example, it also includes a modified compound in which the polyvinyl alcohol is partially acetalized, butyralized, etc., and conventionally known polyvinyl alcohol can be used. The degree of polymerization of the polyvinyl alcohol is not particularly limited, and polyvinyl alcohol generally in the range of 100 or more, preferably 300 to 40,000, can be used. When the degree of polymerization is lower than 100, the water resistance of the functional layer is sometimes reduced. In addition, the saponification degree of the polyvinyl alcohol is not particularly limited, and is preferably a polyvinyl acetate saponified product in the range of 50 mol% or more, more preferably 70 to 99 mol%, further preferably 80 to 98 mol%, and particularly preferably 86 to 97 mol%.
[0168] The lower limit of the content of the polymer in the functional layer is usually 0% by weight or more, preferably 3% by weight or more, more preferably 5% by weight or more, further preferably 10% by weight or more, and particularly preferably 15% by weight or more. Moreover, the upper limit is usually 80% by weight or less, preferably 70% by weight or less, more preferably 60% by weight or less, further preferably 55% by weight or less, and particularly preferably 50% by weight or less. By using the polymer in the above range, the ease of formation of the image forming material and the adhesion with the substrate film are improved, and in addition, there is a tendency to become easy to achieve the excellent appearance brought by improving the wettability of the substrate film when the functional layer is provided by coating.
[0169] (Crosslinking agent)
[0170] In order to increase the strength of the functional layer and improve the fixability with the image forming material, it is preferred to further contain a crosslinking agent. In this case, the crosslinked functional layer contains a crosslinked structure derived from the crosslinking agent. That is, the functional layer containing a crosslinking agent refers to a functional layer formed by curing a coating liquid containing a crosslinking agent.
[0171] In addition, by including a crosslinking agent in the functional layer, there is a tendency to impart a property of improving wettability to the substrate film. According to the research of the present inventors, when the substrate, i.e., the polyester film, contains a polymer incompatible with polyester, especially polyolefin, the wettability is poor when the functional layer is provided by coating, and sometimes the coating liquid is repelled. However, it was unexpectedly found that the wettability is greatly improved by including a crosslinking agent in the functional layer.
[0172] As cross-linking agent, known materials in the past can be used, for example, oxazoline compounds, isocyanate compounds, epoxy compounds, melamine compounds, carbodiimide compounds, silane coupling compounds, hydrazine compounds, aziridine compounds etc. can be enumerated. Among them, preferred oxazoline compounds, isocyanate compounds, epoxy compounds, melamine compounds, carbodiimide compounds, silane coupling compounds. In order to further strengthen the intensity of functional layer, preferred melamine compounds, oxazoline compounds, in order to improve the adhesion with substrate film, preferred oxazoline compounds, isocyanate compounds, epoxy compounds, carbodiimide compounds, particularly preferred oxazoline compounds, isocyanate compounds.
[0173] As cross-linking agent, above-mentioned materials can be used, among them, in order to improve wettability, preferred oxazoline compounds, isocyanate compounds, epoxy compounds, silane coupling compounds, wherein, more preferably oxazoline compounds, isocyanate compounds.That is, if comprehensive consideration, then as the most preferred material of cross-linking agent is oxazoline compounds or isocyanate compounds.In addition, these cross-linking agents can use 1 kind, also can be used in combination of 2 or more kinds.
[0174] As the oxazoline compound used as above-mentioned crosslinking agent, the polymkeric substance that preferably contains oxazoline group particularly, can be made separately or by polymerization with other monomers by the monomer containing addition polyable oxazoline group.The monomer containing addition polyable oxazoline group can enumerate 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, 2-isopropenyl-5-ethyl-2-oxazoline etc., can use one or more mixtures among them.
[0175] Among them, 2-isopropenyl-2-oxazoline is also easily available in industry and is suitable. As long as other monomers are monomers that can be copolymerized with the monomer containing the addition-polymerizable oxazoline group, there is no restriction, for example, (meth) acrylic acid esters such as alkyl (meth) acrylates; unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, styrene sulfonic acid and its salts (sodium salt, potassium salt, ammonium salt, tertiary amine salt, etc.); unsaturated nitriles such as acrylonitrile and methacrylonitrile; unsaturated amides such as (meth) acrylamide, N-alkyl (meth) acrylamide, N, N-dialkyl (meth) acrylamide; vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether and ethyl vinyl ether; α-olefins such as ethylene and propylene; halogen-containing α, β-unsaturated monomers such as vinyl chloride, vinylidene chloride, and vinyl fluoride; α, β-unsaturated aromatic monomers such as styrene and α-methyl styrene, etc., and one or more monomers thereof can be used. Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a tert-butyl group, a 2-ethylhexyl group, and a cyclohexyl group.
[0176] The isocyanate compound used as the crosslinking agent is an isocyanate or a compound having an isocyanate derivative structure represented by a blocked isocyanate. Examples of isocyanates include aromatic isocyanates such as toluene diisocyanate, xylylene diisocyanate, methylene diphenyl diisocyanate, phenylene diisocyanate, and naphthalene diisocyanate; aliphatic isocyanates having an aromatic ring such as α,α,α',α'-tetramethylxylylene diisocyanate; aliphatic isocyanates such as methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate; alicyclic isocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, methylenebis(4-cyclohexyl isocyanate), and isopropylidene dicyclohexyl diisocyanate.
[0177] In addition, polymers and derivatives such as biuret compounds, isocyanurate compounds, uretdione compounds, carbodiimide modified bodies of these isocyanates can also be enumerated. They can be used alone or in combination. Among the above-mentioned isocyanates, in order to avoid the yellowing caused by ultraviolet rays, aliphatic or alicyclic isocyanates are more preferred than aromatic isocyanates.
[0178] When the isocyanate is used in a blocked state, examples of the blocking agent include bisulfites, phenolic compounds such as phenol, cresol, and ethylphenol, alcohol compounds such as propylene glycol monomethyl ether, ethylene glycol, benzyl alcohol, methanol, and ethanol, active methylene compounds such as dimethyl malonate, diethyl malonate, methyl isobutyrylacetate, methyl acetoacetate, ethyl acetoacetate, and acetylacetone, thiol compounds such as butyl mercaptan and dodecyl mercaptan, lactam compounds such as ε-caprolactam and δ-valerolactam, amine compounds such as diphenylaniline, aniline, and ethyleneimine, amide compounds such as acetanilide and acetamide, and oxime compounds such as formaldehyde, acetoxime, acetone oxime, methyl ethyl ketone oxime, and cyclohexanone oxime. These compounds may be used alone or in combination of two or more. Among the above, isocyanate compounds blocked with an active methylene compound are particularly preferred from the viewpoint of adhesion to the substrate film and wettability to the substrate film.
[0179] The isocyanate compounds may be used as a monomer or as a mixture or combination with various polymers. In terms of improving the dispersibility and crosslinking properties of the isocyanate compounds, it is also preferred to use them as a mixture or combination with a polyester resin or a polyurethane resin.
[0180] Examples of the epoxy compound used as the crosslinking agent include condensates of epichlorohydrin with hydroxyl groups or amino groups of ethylene glycol, polyethylene glycol, glycerol, polyglycerol, bisphenol A, etc.; polyepoxy compounds, diepoxy compounds, monoepoxy compounds, glycidylamine compounds, etc. Examples of the polyepoxy compound include sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether, triglycidyl tris(2-hydroxyethyl)isocyanate, glycerol polyglycidyl ether, and trimethylolpropane polyglycidyl ether; examples of the diepoxy compound include neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, resorcinol diglycidyl ether, ethylene glycol diglycidyl ether, etc. Glyceryl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, polytetramethylene glycol diglycidyl ether; as the monoepoxy compound, for example, allyl glycidyl ether, 2-ethylhexyl glycidyl ether, phenyl glycidyl ether can be mentioned, and as the glycidylamine compound, N,N,N',N'-tetraglycidyl-meta-xylylenediamine, 1,3-bis(N,N-diglycidylamino)cyclohexane can be mentioned.
[0181] The melamine compound used as the crosslinking agent refers to a compound having a melamine skeleton in the compound, for example, an alkanolated melamine derivative, a compound partially or completely etherified by reacting the alkanolated melamine derivative with an alcohol, and a mixture thereof. As the alcohol used in the etherification, methanol, ethanol, isopropanol, n-butanol, isobutanol, etc. are suitable. In addition, as the melamine compound, a monomer or a polymer of more than 2 polymers, or a mixture thereof can also be used. If the reactivity of various compounds is taken into consideration, it is preferred that a hydroxyl group is contained in the melamine compound. Furthermore, a substance formed by co-condensing urea or the like with a part of melamine can also be used, and a catalyst can also be used to improve the reactivity of the melamine compound.
[0182] The carbodiimide compound used as the crosslinking agent is a compound having one or more carbodiimide or carbodiimide derivative structures in the molecule. In order to improve the strength of the functional layer, a polycarbodiimide compound having two or more carbodiimide structures in the molecule is preferred.
[0183] The carbodiimide compounds used as the crosslinking agent can be synthesized by the conventionally known techniques, usually by the condensation reaction of diisocyanate compounds. As diisocyanate compounds, there are no particular limitations, and aromatic and aliphatic systems can be used, and specifically, toluene diisocyanate, xylene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexyl diisocyanate, dicyclohexylmethane diisocyanate, etc. can be cited.
[0184] Furthermore, to improve the water solubility and water dispersibility of the polycarbodiimide compound, a surfactant or a hydrophilic monomer such as polyalkylene oxide, quaternary ammonium salt of dialkylamino alcohol, or hydroxyalkylsulfonate may be added and used within a range that does not eliminate the effects of the present invention.
[0185] The silane coupling compound used as the crosslinking agent is an organic silicon compound having an organic functional group and a hydrolyzable group such as an alkoxy group in one molecule. For example, epoxy group-containing compounds such as 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; vinyl group-containing compounds such as vinyltrimethoxysilane and vinyltriethoxysilane; styrene group-containing compounds such as p-styryltrimethoxysilane and p-styryltriethoxysilane; (meth)acryloyl group-containing compounds such as 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, and 3-(meth)acryloxypropylmethyldiethoxysilane; 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and 3-aminopropyltrimethoxysilane. Silane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltriethoxysilane and other amino group-containing compounds; tris(trimethoxysilylpropyl)isocyanurate, tris(triethoxysilylpropyl)isocyanurate and other isocyanurate-containing compounds; 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropylmethyldiethoxysilane and other mercapto group-containing compounds, etc.
[0186] Among the above compounds, epoxy-containing silane coupling compounds, vinyl- or (meth)acryloyl-containing double bond-containing silane coupling compounds, and amino-containing silane coupling compounds are more preferred from the viewpoint of the strength of the functional layer and the adhesion to the substrate film.
[0187] It should be noted that the crosslinking agent contained in the functional layer usually exists in the state of polymer and reaction with the crosslinking agent itself during the drying process and the film forming process. Therefore, the functional layer in the laminated white film 1 exists in the form of unreacted products of these crosslinking agents, reacted compounds, or mixtures thereof (compounds derived from the crosslinking agent).
[0188] The lower limit of the content of the crosslinking agent in the functional layer is usually 0% by weight or more, preferably 3% by weight or more, more preferably 5% by weight or more, further preferably 8% by weight or more, and particularly preferably 10% by weight or more. Moreover, the upper limit is usually 80% by weight or less, preferably 70% by weight or less, more preferably 60% by weight or less, further preferably 50% by weight or less, and particularly preferably 40% by weight or less. By using it in the above range, the strength of the functional layer can be improved, and in addition, there is a tendency to improve the adhesion with the substrate film and to easily achieve the excellent appearance brought about by the wettability of the substrate film when the functional layer is set by coating. Here, the content of the crosslinking agent refers to the ratio of the non-volatile components in the raw material (coating solution) before the crosslinking reaction, and also refers to the same meaning in the functional layer after the crosslinking reaction.
[0189] (Other ingredients)
[0190] In order to improve adhesion and lubricity, the functional layer may contain particles without prejudice to the gist of the present invention. Furthermore, the functional layer may contain defoamers, coating improvers, thickeners, organic lubricants, ultraviolet absorbers, antioxidants, foaming agents, etc.
[0191] (Thickness of functional layer)
[0192] The thickness of the functional layer is usually 0.001 to 3 μm, preferably 0.005 to 1 μm, more preferably 0.01 to 0.5 μm, further preferably 0.02 to 0.3 μm, and most preferably 0.03 to 0.2 μm. When the thickness of the functional layer is within the above range, it tends to be easier to achieve both good antistatic performance and mold release performance.
[0193] (Configuration of functional layer)
[0194] The functional layer may be provided on one side of the polyester film serving as the substrate, or may be provided on both sides of the polyester film.
[0195] When the functional layer is provided on both sides, a film that can be used as a recording material can be formed on both sides, and the operability of the film is optimized, which is preferred in terms of performance compared to the case of one side. In addition, by providing the functional layer on both sides, there is a tendency that the curling property caused by environmental changes such as temperature and humidity can also be improved.
[0196] (Antistatic properties of functional layer)
[0197] The antistatic performance of the functional layer is usually 1×10 13 Ω or less, preferably 1×10 12 Ω or less, more preferably 5×10 11 Ω or less, more preferably 1×10 11Ω or less, particularly preferably 5×10 10 Ω or less. When it is within the above range, there is a tendency to be a film that is effective in preventing adhesion between films and preventing the adhesion of dust, etc. Therefore, when used as a recording material of copy paper or printing paper to which a toner image can be appropriately transferred by an electronic photograph method, a thermal transfer method, etc., it is possible to prevent overlapping feeding during paper transportation in a copier or multifunction machine, and to prevent adhesion between papers when handling papers.
[0198] <Method for producing the laminated white film 1>
[0199] Hereinafter, the method for producing the laminated white film 1 will be specifically described. However, the present invention is not particularly limited to the following examples as long as the gist of the present invention is satisfied.
[0200] First, the mixed raw materials dried or undried by a known method are supplied to a melt extruder, heated to a temperature higher than the melting point of each polymer, and melt-kneaded. Next, the molten polymer is introduced into a die to produce a molten sheet.
[0201] It should be noted that, in the case of manufacturing a polyester film stacked with more than two layers, the raw materials mixed in each layer are supplied to each melt extruder, heated to a temperature above the melting point of each polymer and melt kneaded. Then, the molten polymer of each layer is usually introduced into a mold through a multi-manifold or a feed head and stacked.
[0202] Next, the molten sheet extruded from the die is quenched and solidified on a rotating cooling drum to a temperature below the glass transition temperature, thereby obtaining a substantially amorphous unoriented sheet. In the above case, in order to improve the planarity of the sheet, it is preferred to increase the adhesion between the sheet and the rotating cooling drum, preferably using an electrostatic application densification method and / or a liquid coating densification method.
[0203] The sheet obtained as described above is stretched to form a film. Fine independent cavities contained in the polyester film are generated by the stretching.
[0204] Specifically, the unstretched sheet is preferably stretched 2.5 to 5 times in the longitudinal direction (longitudinal direction) at 70 to 150° C. to form a longitudinal uniaxially stretched film. The longitudinal uniaxially stretched film is preferably stretched 3 to 5 times in the width direction (transverse direction) at 70 to 160° C., and heat treated for 5 to 600 seconds, preferably 8 to 300 seconds, at a temperature of usually 200 to 250° C., preferably 210 to 240° C., and more preferably 215 to 240° C.
[0205] By adjusting the heat treatment temperature within the above temperature range, the melt viscosity of the polymer incompatible with the polyester can be adjusted, and the roughness of the film surface can be adjusted.
[0206] The conditions of the above-mentioned heat treatment process not only affect the heat shrinkage rate of the film, but also affect the arithmetic mean roughness (Ra) of the film surface. That is, by setting the high temperature in the above-mentioned range, the fine cavities formed by the polymer incompatible with polyester existing on the surface or in the surface layer in the case of a laminated structure are melted. By appropriately reducing the surface roughness, the text and image formed on the surface of the film by printing can be easily peeled off and removed. As a result, the film can be reused as a recording material for copy paper and printing paper.
[0207] After the heat treatment step, it is preferred to relax the fabric by 2 to 20% in the longitudinal and / or transverse directions in the highest temperature zone of the heat treatment and / or the cooling zone at the heat treatment outlet. In addition, longitudinal stretching and transverse stretching may be added as needed.
[0208] (Method for forming functional layer)
[0209] The polyester film obtained by the above-mentioned production method has a functional layer laminated on at least one surface.
[0210] The functional layer can be provided by various known methods such as coating, coextrusion, and transfer, among which, provision by coating is preferred from the viewpoint of efficient production and imparting performance.
[0211] The above-mentioned coating method can use, for example, previously known coating methods such as gravure coating, reverse roll coating, die coating, air knife coating, blade coating, rod coating, rod coating, curtain coating, knife coating, transfer roll coating, press coating, impregnation coating, lip coating, spray coating, calender coating, and extrusion coating.
[0212] The functional layer can be provided by in-line coating in the polyester film production process by treating the film surface, or by off-line coating on a pre-fabricated film outside the system. Among them, the functional layer is more preferably formed by in-line coating.
[0213] Online coating is a method of coating in the process of polyester film manufacturing, specifically, the following method: after the polyester is melted and extruded, it is stretched and heat-fixed and coated in any stage until it is rolled up. Usually, it is coated on any of the unstretched sheets obtained by melting and quenching, the uniaxially stretched film after stretching, the biaxially stretched film before heat fixing, and the film before rolling up after heat fixing. It is not limited to the following, for example, in biaxial stretching in sequence, it is particularly excellent to stretch along the width direction (transverse direction) after being coated on the uniaxially stretched film after stretching in the length direction (longitudinal direction). According to the above method, film making and functional layer formation can be carried out simultaneously, so there is an advantage in manufacturing cost. In addition, in order to stretch after coating, the thickness of the functional layer can also be changed according to the stretching ratio, and compared with offline coating, film coating can be carried out more easily. In addition, by arranging the functional layer on the film before stretching, the functional layer can be stretched together with the substrate film, thereby, the functional layer can be firmly adhered to the substrate film.
[0214] Furthermore, in the manufacture of biaxially stretched polyester film, the film can be constrained in the longitudinal and transverse directions by stretching while clamping the film ends in a fixture, etc., and in the heat fixing process, high temperature can be applied while maintaining the flatness without introducing wrinkles, etc. Therefore, if online coating is performed, the heat treatment implemented after coating can form a high temperature that cannot be achieved by other methods, so the film-forming property of the functional layer is improved, and the functional layer can be more firmly fitted to the substrate film, and further, a strong functional layer can be formed, the functional layer can be prevented from falling off, and the antistatic performance and demoulding performance can be improved. In addition, when a raw material (coating liquid) containing a crosslinking agent is used to form a functional layer, a crosslinking reaction can be carried out by utilizing the high temperature during heat fixing.
[0215] As a method for forming a functional layer, it is preferred to manufacture a laminated white film in the following manner: the above series of compounds are formed into a solution or a dispersion of a solvent, and a liquid with a solid content concentration adjusted to about 0.1 to 80% by weight is applied to a polyester film. In particular, in the case of an online coating arrangement, an aqueous solution or an aqueous dispersion is more preferred. For the purpose of improving the dispersibility in water, improving the film-forming property, etc., a small amount of an organic solvent may be contained in the coating liquid. In addition, only one organic solvent may be used, or two or more organic solvents may be used as appropriate.
[0216] The drying and curing conditions when forming the functional layer are not particularly limited. In the case of a coating method, the drying temperature of a solvent such as water used in the coating solution is usually 70 to 150° C., preferably 80 to 130° C., and more preferably 90 to 120° C. The drying time is preferably 3 to 200 seconds, preferably 5 to 120 seconds.
[0217] In order to improve the strength of the functional layer, the film production process preferably undergoes a heat treatment step at a temperature of generally 150 to 270° C., preferably 170 to 250° C., and more preferably 180 to 240° C. The time for the heat treatment step is preferably 5 to 600 seconds, preferably 8 to 300 seconds.
[0218] Furthermore, the heat treatment may be combined with the irradiation with active energy rays such as ultraviolet ray irradiation, if necessary. The polyester film constituting the laminated white film 1 may be subjected to a surface treatment such as a corona treatment or a plasma treatment in advance.
[0219] <Image forming materials, etc.>
[0220] The laminated white film 1 can be provided with characters and images made of a thermoplastic resin containing an image forming substance on the functional layer.
[0221] Here, the characters and images can be provided by a conventionally known method and can be obtained by printing using a copier, a printer, or the like.
[0222] On the other hand, as the thermoplastic resin used in the image forming material and the like, a conventionally known material may be used.
[0223] The image forming material is not limited. That is, the above-mentioned "image forming material, etc." generally includes all materials that can form an image on a recording material, and may be in any form such as solid particles, suspensions, solutions, etc., and also includes inks.
[0224] In addition, the colorant is not limited, and any of a pigment, a dye, a colored compound, etc. can be used. Among them, a toner in which a pigment is dispersed in a thermoplastic resin to form fine particles is suitable.
[0225] <Resin layer>
[0226] The laminated white film 1 may further include a resin layer on the image forming material or the like or on the functional layer.
[0227] The resin layer may be provided for the purpose of reusing the laminated white film or the like and for the purpose of peeling and removing characters and images from the film together with the resin layer.
[0228] As the resin layer, a conventionally known material can be used, and a curable resin layer formed of a curable resin composition is preferred.
[0229] Examples of the curable resin layer include a thermosetting resin layer formed from a resin composition cured by heating, an active energy ray-curable resin layer formed from a resin composition cured by irradiation with active energy rays, etc. Among them, the active energy ray-curable resin layer is preferred from the viewpoint of easy peeling and removal without leaving any text or image.
[0230] As the active energy ray curable resin layer, there can be mentioned an ultraviolet curable resin layer, an electron beam curable resin layer, a visible light curable resin layer, etc. If the ease of handling and curability are considered, the aforementioned ultraviolet curable resin layer is preferred. As an example of the active energy ray curable resin layer, for example, a hard coat layer can be mentioned.
[0231] The material used in the active energy ray curable resin layer is not particularly limited. For example, the cured product of reactive silicon compounds such as monofunctional (meth) acrylate, multifunctional (meth) acrylate, tetraethoxysilane, etc. can be cited. Among them, from the viewpoint of taking into account both productivity and hardness, the polymerized cured product of the composition of (meth) acrylate that particularly preferably comprises active energy ray curable is preferably used. In addition, in order to peel off and remove the image from the laminated white film, when the resin layer is provided, by forming the above-mentioned material, there is a tendency that a good peeling and removal characteristic can be exerted.
[0232] The composition containing active energy ray-curable (meth)acrylate is not particularly limited. For example, a composition obtained by mixing one or more of known monofunctional (meth)acrylates, difunctional (meth)acrylates, and multifunctional (meth)acrylates; a commercially available product as an active energy ray-curable hard coating resin material; or a composition obtained by further adding other components to the range that does not impair the purpose of the present embodiment can be used.
[0233] The active energy ray-curable monofunctional (meth)acrylate is not particularly limited. Examples thereof include methyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate and other alkyl (meth)acrylates, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate and other hydroxyalkyl (meth)acrylates, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, methoxypropyl (meth)acrylate, ethoxypropyl (meth)acrylate and other (meth)acrylates. (meth)acrylates such as alkoxyalkyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, and phenoxypropyl (meth)acrylate; (meth)acrylates containing an amino group such as diaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate; methoxyethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate; ethylene oxide-modified (meth)acrylates such as phenylphenol ethylene oxide-modified (meth)acrylate; glycidyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, and (meth)acrylic acid; and the like.
[0234] The active energy ray-curable difunctional (meth)acrylate is not particularly limited, and examples thereof include 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, alkanediol di(meth)acrylates such as tricyclodecane dihydroxymethyl di(meth)acrylate, bisphenol-modified di(meth)acrylates such as bisphenol A ethylene oxide-modified di(meth)acrylate and bisphenol F ethylene oxide-modified di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, urethane di(meth)acrylate, epoxy di(meth)acrylate, and the like.
[0235] The active energy ray-curable multifunctional (meth)acrylate is not particularly limited, and examples thereof include dipentaerythritol hexa(meth)acrylate, pentaerythritol tetra(meth)acrylate, di(trimethylol)propane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, isocyanuric acid-modified tri(meth)acrylate such as isocyanuric acid ethylene oxide-modified tri(meth)acrylate and ε-caprolactone-modified tri(acryloyloxyethyl)isocyanurate, urethane acrylates such as pentaerythritol triacrylate hexamethylene diisocyanate urethane prepolymer, pentaerythritol triacrylate toluene diisocyanate urethane prepolymer, and dipentaerythritol pentaacrylate hexamethylene diisocyanate urethane prepolymer.
[0236] The other components contained in the composition containing active energy ray-curable (meth)acrylate are not particularly limited. For example, inorganic or organic microparticles, polymerization initiators, polymerization inhibitors, antioxidants, antistatic agents, dispersants, surfactants, light stabilizers, and leveling agents can be cited. In addition, when the film is formed and dried in the wet coating method, an arbitrary amount of solvent can be added.
[0237] When a resin layer is provided in order to peel off characters and images from a laminated white film, the peeling and removal process is usually carried out in an office or the like rather than in a factory for manufacturing the film. Therefore, it is preferred that the film does not contain a solvent when used indoors such as in an office. As the resin (resin liquid) used to form the resin layer, the content of the solvent is preferably 10% by weight or less, more preferably 5% by weight or less, further preferably 3% by weight or less, particularly preferably 1% by weight or less, and most preferably does not contain a solvent (does not contain it intentionally).
[0238] The resin layer may be formed by a common wet coating method such as a roll coating method or a die coating method, an extrusion method, etc. The formed resin layer may be subjected to a curing reaction by heating or irradiation with active energy rays such as ultraviolet rays or electron beams as required.
[0239] <<Second embodiment>>
[0240] As an example of the second embodiment for carrying out the present invention, a laminated white polyester film (also referred to as a “laminated white film”) 10 will be described.
[0241] <Laminated white polyester film 10>
[0242] A laminated white polyester film 10 (referred to as "the present laminated white polyester film 10") as an example of a method for implementing the present invention is characterized in that it is a laminated film having at least two layers of polyester-based resin, at least the surface layer of which contains polyester and a polymer incompatible with the polyester.
[0243] <Layered structure>
[0244] The laminated structure of the laminated white polyester film 10 is not particularly limited to 2 layers, 3 layers, 4 layers or more layers as long as it does not deviate from the gist of the present invention. Among them, a 3-layer structure (surface layer / middle layer / surface layer) consisting of two surface layers and an intermediate layer is preferred.
[0245] The laminated structure of two layers refers to a structure of two surface layers, and specifically includes a structure of two layers having different compositions such as the type of polyester constituting each layer and the particles contained therein.
[0246] <Surface>
[0247] The surface layer of the laminated white polyester film 10 preferably contains at least polyester as a main component resin and a polymer incompatible with polyester.
[0248] Here, "main component resin" refers to the resin with the largest content in the resin components constituting the surface layer. It can be assumed that the main component resin accounts for 30% or more, 50% or more, or 80% or more (including 100% by mass) of the resin components constituting the surface layer.
[0249] (Polyester)
[0250] The polyester constituting the present laminated white polyester film 10 is the same as the polyester serving as the main component resin of the polyester film serving as the base material or the polyester resin layer in the present laminated white film 1 described above.
[0251] (Polymers incompatible with polyester)
[0252] By including a polymer incompatible with the above-mentioned polyester in the present laminated white polyester film 10, the polyester film stretched at least in a uniaxial direction can contain countless fine cavities. The present laminated white polyester film 10 scatters light through the aforementioned fine cavities, not only making the white color opaque, but also reducing the apparent density of the present laminated white polyester film 10.
[0253] In particular, by containing a polymer incompatible with polyester in the surface layer of the laminated white polyester film 10, when used as a recording material of copy paper or printing paper, it is possible to easily peel off and remove image forming materials containing thermoplastic resins such as toners printed on the surface of the laminated white polyester film 10. In addition, in order to ensure sufficient hiding power and weight reduction, the intermediate layer may contain a polymer incompatible with polyester as needed.
[0254] The polymer incompatible with polyester is the same as the "polymer incompatible with polyester" explained in the above-mentioned laminated white film 1.
[0255] The lower limit of the content of "polymers incompatible with polyester" in the surface layer of the laminated white polyester film 10 is usually 1% by weight or more, preferably 2% by weight or more, more preferably 3% by weight or more, further preferably 5% by weight or more, and particularly preferably 8% by weight or more. By using it in the above range, the amount of fine cavities generated in the film becomes sufficient, the hiding power of the film is improved, and the effect of reducing the apparent density, that is, lightweighting, becomes sufficient. In addition, the lubricity of the film and the note-taking properties of pencils, etc. are also improved, which is also beneficial for printing and conveying properties. Furthermore, it becomes easy to peel off and remove the text and images produced by the image-forming material printed on the surface of the film, and there is a tendency to reuse the film as a recorded material for copy paper and printing paper.
[0256] On the other hand, the upper limit of the content of the polymer incompatible with polyester in the surface layer is usually 70% by weight or less, preferably 50% by weight or less, more preferably 40% by weight or less, further preferably 35% by weight or less, particularly preferably 30% by weight or less, and most preferably 25% by weight or less. By using within this range, the amount of voids generated will not be too much, and there is a tendency to easily suppress breakage during stretching.
[0257] The lower limit of the content of the "polymer incompatible with polyester" in each layer of the laminated white polyester film 10 is usually 1% by weight or more, preferably 2% by weight or more, more preferably 3% by weight or more, further preferably 5% by weight or more, and particularly preferably 8% by weight or more. By using the above range, sufficient hiding power can be obtained, and the effect of reducing the apparent density, that is, weight reduction can be sufficient.
[0258] On the other hand, the upper limit of the content of the polymer incompatible with polyester in each layer of the laminated white polyester film 10 is usually 70% by weight or less, preferably 50% by weight or less, more preferably 40% by weight or less, further preferably 35% by weight or less, particularly preferably 30% by weight or less, and most preferably 25% by weight or less. By using within this range, the amount of voids generated will not be too much, and there is a tendency to easily suppress breakage during stretching.
[0259] When the laminated white polyester film 10 is composed of three or more layers, the intermediate layer may be mixed with recycled products such as the edge portion, the edge portion of the master roll, and the lower portion of the master roll produced when the film is manufactured, within the range that does not impair the main purpose of the present invention. By including the recycled products, it is possible to achieve the effect of reducing costs and reducing environmental loads. In addition to the color tone restriction, from the perspective of the film forming stability caused by the reduction of the intrinsic viscosity, the content of the recycled products in the intermediate layer is preferably set to 95% by weight or less, more preferably 85% by weight or less, further preferably 70% by weight or less, particularly preferably 60% by weight or less, and most preferably 40% by weight or less.
[0260] (Metal compound particles)
[0261] In the present laminated white polyester film 10, metal compound particles may also be contained for the purpose of further improving the hiding power and whiteness. When the polyester film is composed of more than three layers, the layer containing the metal compound particles may be a surface layer or an intermediate layer. In order to effectively improve the hiding power and whiteness, it is preferably contained in the surface layer.
[0262] The metal compound particles used in the present laminated white polyester film 10 tend to complement the white opacity caused by the light scattering effect of fine cavities formed by compounding an incompatible polymer, and thus tend to provide a higher hiding power and whiteness.
[0263] In this case, the metal compound particles are the same as those described in the above-mentioned laminated white film 1.
[0264] The content of the metal compound particles is preferably 1% by weight or more, more preferably 2% by weight or more, and further preferably 3% by weight or more, relative to the entire surface layer of the laminated white polyester film 10 containing the metal compound particles, and the upper limit is usually 30% by weight or less, preferably 20% by weight or less, more preferably 15% by weight or less, further preferably 13% by weight or less, and particularly preferably 10% by weight or less. By setting it to the above range, sufficient hiding power can be given, and it is also cost-effective, and there is a tendency to become the best recording material for copy paper and printing paper instead of paper made of paper.
[0265] (Particles other than metal compound particles)
[0266] In order to improve the handling property and lubricity of the present laminated white polyester film 10 , and in particular to impart lubricity to the surface layer of the present laminated white polyester film 10 , particles other than the metal compound particles exemplified above may be contained.
[0267] In this case, the particles other than the metal compound particles are the same as the “particles other than the metal compound particles” described in the above-mentioned laminated white film 1 .
[0268] (Other ingredients)
[0269] In addition to the above-mentioned particles and the polymer incompatible with polyester, conventionally known antioxidants, heat stabilizers, lubricants, antistatic agents, fluorescent whitening agents, dyes, pigments, etc. may be added to the laminated white polyester film 10 as required. In addition, ultraviolet absorbers, particularly benzoxazinone ultraviolet absorbers, etc. may also be contained depending on the application.
[0270] <Layered structure>
[0271] The laminated white polyester film 10 is preferably a laminated film having at least two layers of the above-mentioned polyester-based resin, wherein at least the surface layer contains polyester and a polymer incompatible with the polyester, and the arithmetic mean roughness (Ra) of the surface layer is less than 950nm.
[0272] If the surface layer contains polyester and a polymer incompatible with the polyester as described above, fine cavities can be provided by stretching, thereby achieving lightness, hiding power, and whitening, and further, the surface roughness can be adjusted, thereby improving the writing properties.
[0273] If the surface layer further contains metal compound particles, the hiding power and whiteness can be further improved, and if particles other than the metal compound particles are further contained, the lubricity can be improved.
[0274] If the intermediate layer other than the surface layer contains the polyester, it may contain a polymer incompatible with the polyester, metal compound particles, and particles other than the metal compound particles as required. From the viewpoint of reducing costs and reducing environmental loads, it is preferred to reduce the content of the metal compound particles and particles other than the metal compound particles as small as possible, and to use polyester as a recycled product.
[0275] <Thickness>
[0276] The thickness of the laminated white polyester film 10 is not particularly limited as long as it is within the range that can be used as a film. It is preferably in the range of 10 to 1000 μm, more preferably 20 to 500 μm, further preferably 30 to 400 μm, and particularly preferably 38 to 350 μm. By using it within the above range, the stiffness and handleability of the film can be sufficient.
[0277] The laminated white polyester film 10 preferably contains metal compound particles or particles other than metal compound particles in the surface layer.
[0278] In order to mix a recycled product in the intermediate layer and to cope with cost reduction and environmental load reduction, it is preferable to form a laminated structure by a co-extrusion method.
[0279] From the above viewpoint, when the polyester film is a laminated structure of more than 3 layers as described above, the thickness of each surface layer is preferably 1 μm to 50 μm, wherein more preferably 2 μm or more or 40 μm or less, wherein more preferably 3 μm or more or 30 μm or less, wherein more preferably 4 μm or more or 25 μm or less. By using it in the above range, the performance of the metal compound particles described later and the particles other than the metal compound particles can be fully utilized, and the manufacturing cost is also suppressed to be cheap.
[0280] <Apparent density>
[0281] The lower limit of the apparent density of the laminated white polyester film 10 is usually 0.7 g / cm 3 Above, preferably 0.75g / cm 3 More preferably 0.8 g / cm 3 By setting the above range, the strength of the film can be maintained, and when the film is used as a recording material instead of information printing medium, i.e., copy paper or printing paper, the clogging of the film during the conveying process in the copier can be reduced, thereby achieving optimal printing.
[0282] On the other hand, the upper limit is usually 1.3 g / cm 3 Below, preferably 1.2g / cm 3 Below, more preferably 1.1 g / cm 3 By setting the above range, the workload when conveying a large amount of printed materials can be reduced, and the reduction of CO2 generated during the conveyance of the film (sheet) can be reduced to reduce the environmental load and reduce costs.
[0283] The apparent density of the polyester film can be adjusted by blending an incompatible polymer having a specific gravity lighter than the polyester as the main component resin and stretching the film in at least one axial direction, but the method is not limited to these.
[0284] <Physical Properties>
[0285] The surface of the laminated white polyester film 10, i.e., the arithmetic mean roughness (Ra) of the surface layer is preferably 950 nm or less, more preferably 850 nm or less, and more preferably 800 nm or less. By using the arithmetic mean roughness (Ra) in the above range, the text and image of the image forming material containing the thermoplastic resin formed by printing on the film surface can be easily peeled off, and there is a tendency that the film can be reused as a recording material of copy paper and printing paper.
[0286] On the other hand, the lower limit of the arithmetic mean roughness (Ra) is preferably 100 nm or more, more preferably 200 nm or more, more preferably 300 nm or more, and more preferably 350 nm or more. By setting it in the above range, the covering property and the conveying property can be sufficient, and a film that is best used as a recording material for copy paper and printing paper can be formed. Furthermore, there is a tendency to have sufficient writing properties.
[0287] In addition, the arithmetic mean roughness (Ra) in the present invention is based on the measurement method used in the examples described later.
[0288] The index representing the yellow hue of the laminated white polyester film 10, i.e., the b value (reflection method), is usually below 0.00, preferably below -0.20, more preferably below -0.40, further preferably below -0.50, particularly preferably below -0.60, and the lower limit is not particularly limited, preferably above -5.0. By using it in the above range, the yellow hue is suppressed, and the whiteness can be made good. And then, when used as the recorded material for color printing, there is a tendency to make the obtained image quality excellent.
[0289] The heat shrinkage of the present laminated white polyester film 10 in the film longitudinal direction (MD) and the film width direction (TD) at 150° C. for 30 minutes is usually 2.8% or less, preferably 2.3% or less, and more preferably 2.0% or less in absolute value.
[0290] If the heat shrinkage ratio is within the above range, when printing on a recording material by an electronic photograph method, a thermal transfer method, etc., the dimensional stability of the film can be prevented from being damaged by the influence of heat, and the occurrence of wrinkles can be suppressed particularly at the edge of the film (sheet), that is, the portion where wrinkles are easily generated, and the phenomenon of distortion and unevenness in text and images and reduction in image quality can be suppressed. In addition, wrinkles cannot disappear once they occur, and therefore, it becomes impossible to reuse the recording material as copy paper or printing paper, so it is preferred to avoid wrinkles as much as possible.
[0291] The hiding power (OD) of the laminated white polyester film 10 is measured by a Macbeth densitometer for a single film and is usually 0.30 or more, preferably 0.35 or more, more preferably 0.40 or more, and further preferably 0.45 or more. By using the above range, the back image protrusion when the whole surface is printed on both sides of the film can be reduced, and good quality text and images can be obtained. On the other hand, the upper limit of the hiding power (OD) is not particularly limited. If the balance of other physical properties is considered, it is preferably 1.0 or less, and more preferably 0.9 or less.
[0292] The whiteness of the laminated white polyester film 10 is measured by a colorimeter to measure the Hunter whiteness (Wb) of a single film, and the lower limit is usually 80.0% or more, preferably 81.0% or more, more preferably 82.0% or more, further preferably 83.0% or more, and particularly preferably 83.5% or more. By making the whiteness within the above range, when the recorded material is used as an information printing medium, i.e., copy paper, printing paper, etc. instead of paper, especially when color printing is performed, the text and image become high-precision and tend to be preferred in quality. In addition, it also depends on the purpose of use. Therefore, in order to reflect the sense of luxury, it is preferably higher, and the upper limit is not limited. On the other hand, when used for purposes that focus on gloss, the upper limit of the preferred range is 95.0% or less.
[0293] <Functional layer>
[0294] A functional layer may be provided on at least one surface of the laminated white polyester film 10 .
[0295] The functional layer can function as a recorded layer on which the image forming material is directly attached. The recorded layer in the present invention is a layer that not only fixes the attached image forming material but also removes the image forming material together with the resin layer when the resin layer described later is set.
[0296] The functional layer preferably has antistatic properties and mold release properties.
[0297] In order to reduce the apparent density, whiten the printed text and image such as the image forming material containing thermoplastic resin, the laminated white polyester film 10 preferably has a polyester resin layer containing polyester and a polymer incompatible with polyester, and more preferably has the polyester resin layer on the surface layer. However, when a functional layer is provided, it is judged that it tends to be difficult to achieve the performance of easily stripping and removing the text and image such as the image forming material on the surface layer, so it is preferred that the functional layer also has a demolding property. That is, after printing, in order to provide a demolding property so that the text and image forming material such as the toner containing thermoplastic resin formed on the surface of the film can be appropriately stripped and removed, it is preferred that the functional layer contains a demolding agent.
[0298] The laminated white polyester film 10 is intended to prevent the adhesion of sheets of paper when used as a recording material for copy paper or printing paper to which a toner image can be appropriately transferred by an electronic photographic method, a thermal transfer method, etc., during paper transportation in a copier or a multifunction machine, or during paper handling. Furthermore, in order to prevent dust from adhering and to form a film of good quality or a film printed product with good image quality, the functional layer preferably has antistatic properties.
[0299] From the above viewpoints, it is preferred that a functional layer containing an antistatic agent is provided on at least one surface.
[0300] In order to improve the ease of forming the image forming material and the fixability and to improve the wettability to the base film when the functional layer is provided by coating, the functional layer further preferably contains a polymer (a polymer other than the antistatic agent and release agent).
[0301] It was found that by adding an antistatic agent, a release agent and a polymer to the functional layer to impart appropriate release properties, the function of fixing image-forming materials on the film surface and the function of stripping and removing image-forming materials can be more appropriately obtained. That is, it was found that a method of achieving mutually opposite properties such as fixability and stripping properties in one functional layer is more highly realized. Considering that the stripping property cannot be realized in a conventional functional layer with a fixing property, and on the other hand, the fixing property cannot be realized in a conventional functional layer with a stripping property, it can be said that this technology is a technology with a very high effect. In addition, even if a functional layer with a fixing property is stacked with a functional layer with a stripping property, it is difficult to reflect any performance, and only the performance of the functional layer in the outermost layer is reflected.
[0302] The antistatic agent, the release agent, and the polymer used in the present laminated white polyester film 10 are the same as the antistatic agent, the release agent, and the polymer used in the present laminated white film 1 .
[0303] When the present laminated polyester film has the above-mentioned functional layer, the preferred ranges of the b value, heat shrinkage, hiding power (OD) and whiteness of the present laminated polyester film are also the same as the above-mentioned numerical ranges.
[0304] <Manufacturing method>
[0305] Hereinafter, a method for producing the laminated white polyester film 10 will be specifically described. The present invention is not particularly limited to the following examples as long as the gist of the present invention is satisfied.
[0306] First, the raw materials mixed in each layer, which have been dried or undried by a known method, are supplied to each melt extruder, heated to a temperature above the melting point of each polymer, and melt-kneaded. Next, the molten polymer of each layer is usually introduced into a mold through a multi-manifold or a feed head and stacked.
[0307] Next, the molten sheet extruded from the die is quenched and solidified on a rotating cooling drum to a temperature below the glass transition temperature, thereby obtaining a substantially amorphous unoriented sheet. In the above case, in order to improve the planarity of the sheet, it is preferred to increase the adhesion between the sheet and the rotating cooling drum, preferably using an electrostatic application densification method and / or a liquid coating densification method.
[0308] The sheet obtained as described above is stretched to form a film. Fine independent cavities contained in the polyester film are generated by the stretching.
[0309] Regarding the stretching conditions, it is preferred that the unstretched sheet is preferably stretched to 2.5 to 5 times at 70 to 150° C. in the length direction (longitudinal direction) to form a longitudinal uniaxially stretched film, and then stretched 3 to 5 times at 70 to 160° C. in the width direction (transverse direction), and heat treated at usually 200 to 250° C., preferably 210 to 240° C., and more preferably 215 to 240° C. for usually 5 to 600 seconds, preferably 8 to 300 seconds.
[0310] The conditions of the above-mentioned heat treatment process not only affect the heat shrinkage rate of the film, but also affect the arithmetic mean roughness (Ra) of the surface layer of the film. That is, by setting the high temperature in the above-mentioned range, the fine cavities formed by the polymer incompatible with polyester on the surface of the surface layer are melted. By appropriately reducing the surface roughness, the text and image such as the image forming material containing the thermoplastic resin formed on the surface of the film by printing can be easily peeled off. In this way, the film can be reused as a recording material for copy paper and printing paper.
[0311] After the heat treatment step, it is preferred to relax the fabric by 2 to 20% in the longitudinal and / or transverse directions in the highest temperature zone of the heat treatment and / or the cooling zone at the heat treatment outlet. In addition, longitudinal stretching and transverse stretching may be added as needed.
[0312] The method for forming the functional layer in the laminated white polyester film 10 is described below. The functional layer can be provided by various known methods such as coating, coextrusion, and transfer. Among them, it is preferably provided by coating from the viewpoint of efficient production and imparting performance.
[0313] The coating method may be in-line coating in which the surface of the polyester film is treated during the film-forming process, or in-line coating in which the film is coated on a pre-formed film outside the system. In-line coating is more preferred.
[0314] Online coating is a method of coating in the process of polyester film manufacturing, specifically, the following method: after the polyester is melted and extruded, it is stretched and heat-fixed and coated in any stage until it is rolled up. Usually, it is coated on any of the unstretched sheets obtained by melting and quenching, the uniaxially stretched film after stretching, the biaxially stretched film before heat fixing, and the film before rolling up after heat fixing. It is not limited to the following, for example, in biaxial stretching in sequence, in particular, the method of stretching in the transverse direction after being coated on the uniaxially stretched film after stretching in the length direction (longitudinal direction) is excellent. According to the above method, film making and functional layer formation can be carried out simultaneously, so there is an advantage in manufacturing cost. In addition, in order to stretch after coating, the thickness of the functional layer can also be changed according to the stretching ratio, and compared with offline coating, film coating can be carried out more easily. In addition, by arranging the functional layer on the film before stretching, the functional layer can be stretched together with the substrate film, thereby, the functional layer can be firmly adhered to the substrate film. Furthermore, in the production of biaxially stretched polyester film, the film can be constrained in the longitudinal and transverse directions by stretching while holding the film ends with a clamp or the like, and in the heat fixing process, a high temperature can be applied while maintaining the flatness without introducing wrinkles, etc. Therefore, the heat treatment performed after coating can form a high temperature that cannot be achieved by other methods, so that the film forming property of the functional layer is improved, the functional layer and the base film can be more firmly adhered, and further, a strong functional layer can be formed, the functional layer can be prevented from falling off, and the antistatic performance and demolding performance can be improved.
[0315] <Image forming material>
[0316] On the surface of the surface layer of the laminated white polyester film 10 where the functional layer is not provided or on the surface where the functional layer is provided, characters or images made of a thermoplastic resin containing an image forming substance or the like can be provided.
[0317] The characters and images can be provided by a conventionally known method and can be obtained by printing using a copier, a printer, etc. In addition, conventionally known materials can also be used for thermoplastic resins such as image forming materials.
[0318] <Resin layer>
[0319] The laminated white polyester film 10 may further include a resin layer on characters and images containing a thermoplastic resin such as an image forming substance.
[0320] The resin layer may be provided for the purpose of reusing the laminated white film or the like and for the purpose of peeling and removing characters and images from the film together with the resin layer.
[0321] As the resin layer, a conventionally known material can be used, and a curable resin layer is preferred.
[0322] Examples of the curable resin layer include a thermosetting resin layer and an active energy ray-curable resin layer. The active energy ray-curable resin layer is preferred because it can be easily removed by peeling without leaving any characters or images.
[0323] As the active energy ray curable resin layer, there can be mentioned an ultraviolet curable resin layer, an electron beam curable resin layer, a visible light curable resin layer, etc. If the ease of handling and curability are considered, the aforementioned ultraviolet curable resin layer is preferred. As an example of the active energy ray curable resin layer, for example, a hard coat layer can be mentioned.
[0324] The material used in the active energy ray-curable resin layer is not particularly limited, and examples thereof include cured products of reactive silicon compounds such as monofunctional (meth)acrylates, multifunctional (meth)acrylates, and tetraethoxysilane. Among them, a polymerized cured product of a composition containing an active energy ray-curable (meth)acrylate is particularly preferred from the viewpoint of achieving both productivity and hardness.
[0325] The composition containing active energy ray-curable (meth)acrylate is not particularly limited. For example, a composition obtained by mixing one or more known active energy ray-curable monofunctional (meth)acrylates, difunctional (meth)acrylates, and multifunctional (meth)acrylates; a commercially available active energy ray-curable hard coating resin material; or a composition obtained by further adding other components to the range that does not impair the purpose of the present embodiment can be used.
[0326] The active energy ray-curable monofunctional (meth)acrylate is not particularly limited. Examples thereof include methyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate and other alkyl (meth)acrylates, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate and other hydroxyalkyl (meth)acrylates, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, methoxypropyl (meth)acrylate, ethoxypropyl (meth)acrylate and other (meth)acrylates. (meth)acrylates such as alkoxyalkyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, and phenoxypropyl (meth)acrylate; (meth)acrylates containing an amino group such as diaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate; methoxyethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate; ethylene oxide-modified (meth)acrylates such as phenylphenol ethylene oxide-modified (meth)acrylate; glycidyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, and (meth)acrylic acid; and the like.
[0327] The active energy ray-curable difunctional (meth)acrylate is not particularly limited, and examples thereof include 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, alkanediol di(meth)acrylates such as tricyclodecane dihydroxymethyl di(meth)acrylate, bisphenol-modified di(meth)acrylates such as bisphenol A ethylene oxide-modified di(meth)acrylate and bisphenol F ethylene oxide-modified di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, urethane di(meth)acrylate, epoxy di(meth)acrylate, and the like.
[0328] The active energy ray-curable multifunctional (meth)acrylate is not particularly limited. For example, dipentaerythritol hexa(meth)acrylate, pentaerythritol tetra(meth)acrylate, di(trimethylol)propane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, isocyanuric acid-modified tri(meth)acrylate such as ethylene oxide-modified tri(meth)acrylate, ε-caprolactone-modified tri(acryloyloxyethyl)isocyanurate, pentaerythritol triacrylate hexamethylene diisocyanate urethane prepolymer, pentaerythritol triacrylate toluene diisocyanate urethane prepolymer, dipentaerythritol pentaacrylate hexamethylene diisocyanate urethane prepolymer, and the like urethane acrylates can be cited.
[0329] The other components contained in the composition containing active energy ray-curable (meth)acrylate are not particularly limited. For example, inorganic or organic microparticles, polymerization initiators, polymerization inhibitors, antioxidants, antistatic agents, dispersants, surfactants, light stabilizers, and leveling agents can be cited. In addition, when the film is formed and dried in the wet coating method, an arbitrary amount of solvent can be added.
[0330] For indoor use in offices, etc., it is preferred that the resin (resin liquid) used to form the resin layer has a solvent content of preferably 10 wt % or less, more preferably 5 wt % or less, further preferably 3 wt % or less, particularly preferably 1 wt % or less, and most preferably no solvent (not intentionally contained).
[0331] The resin layer can be formed by a common wet coating method such as a roll coating method or a die coating method, an extrusion method, etc. The formed resin layer may be heated or irradiated with active energy rays such as ultraviolet rays or electron beams to cause a curing reaction as required.
[0332] <Explanation of terms, etc.>
[0333] In the present invention, when described as "X to Y" (X and Y are arbitrary numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", and the meaning of "preferably greater than X" or "preferably less than Y".
[0334] In addition, when described as "X or more" (X is an arbitrary number), unless otherwise specified, it includes the meaning of "preferably greater than X", and when described as "Y or less" (Y is an arbitrary number), unless otherwise specified, it also includes the meaning of "preferably less than Y".
[0335] Example
[0336] Hereinafter, the present invention will be further described in detail according to the examples. The present invention is not limited to the following examples unless it deviates from its purpose. In addition, the determination method used in the present invention is as follows. It should be noted that the various physical properties and the determination methods and definitions in the present invention are as follows.
[0337] <Measurement method>
[0338] (1) Intrinsic viscosity of polyester
[0339] 1 g of polyester from which other components such as polymer components and particles incompatible with the polyester were removed was precisely weighed, and 100 ml of a mixed solvent of phenol / tetrachloroethane = 50 / 50 (weight ratio) was added to dissolve the polyester, and the resultant was measured at 30°C.
[0340] (2) Melt flow index (MFI)
[0341] According to JIS K7210-1995, for amorphous polyolefins, the viscosity is measured at 275° C. and 21.2 N, and for polypropylene, the viscosity is measured at 230° C. and 21.2 N. The higher the value, the lower the melt viscosity of the polymer.
[0342] (3) Arithmetic mean roughness (Ra)
[0343] For the film surface, a non-contact surface and layer cross-section shape measuring system VertScan (registered trademark) R550GML manufactured by MITSUBISHI CHEMICAL SYSTEMS, Inc. was used. An area of 640 μm × 480 μm was measured under CCD camera: SONY HR-50 1 / 3', objective lens: 20 times, lens barrel: 1XBody, zoom lens: No Relay, wavelength filter: 530white, and measurement mode: Wave. The arithmetic mean roughness Ra value was obtained by averaging 10 points using power corrected by a fourth-order polynomial.
[0344] (4) Average particle size
[0345] The particle size was measured by a sedimentation method based on Stokes' resistance method using a centrifugal sedimentation particle size distribution analyzer SA-CP3 manufactured by Shimadzu Corporation. The 50% value of the integral (volume basis) in the equivalent spherical distribution of the particles obtained by the measurement was used as the average particle size.
[0346] (5) Film thickness of functional layer
[0347] The surface of the functional layer was dyed with RuO4 and embedded in epoxy resin. Then, the slices prepared by ultrathin sectioning were dyed with RuO4 and the cross section of the functional layer was observed with a transmission electron microscope (H-7650 manufactured by Hitachi High-Technologies Corporation, accelerating voltage 100 kV) to measure the film thickness.
[0348] (6) Number average molecular weight
[0349] The measurement was performed using gel permeation chromatography (HLC-8120GPC manufactured by Tosoh Corporation). The number average molecular weight was calculated in terms of polystyrene.
[0350] (7) Heating shrinkage
[0351] The sample was treated in an oven maintained at 150° C. for 30 minutes without tension, and the length of the sample before and after was measured. The heat shrinkage ratio was calculated by the following formula.
[0352] Heating shrinkage (%) = {(L0-L1) / L0}×100
[0353] (In the above formula, L0 is the length of the sample before heating treatment, and L1 is the length of the sample after heating treatment)
[0354] The measurement was performed at 5 points each in the longitudinal direction (MD) and the transverse direction (TD) of the film, and the average value in each direction was calculated.
[0355] (8) Surface resistance
[0356] The polyester film was sufficiently humidity-conditioned in a measurement atmosphere of 23°C and 50% RH using a high resistance tester: HP4339B and a measurement electrode: HP16008B manufactured by Hewlett-Packard Japan, Ltd., and the surface resistance value of the functional layer was measured at an applicable voltage of 100 V after 1 minute.
[0357] (9) Hunter Whiteness
[0358] Hunter whiteness (Wb) of a single film was measured using a colorimeter NDH-1001DP (C light source, 2° field of view) manufactured by Nippon Denshoku Industries Co., Ltd. in accordance with the method of JIS P8123-1961. The back side of the film was held by a black plate.
[0359] (10) b value (reflection method)
[0360] The b value of a single film was measured using a colorimeter NDH-1001DP (illuminant C, 2° field of view) manufactured by Nippon Denshoku Industries Co., Ltd. in accordance with the method of JIS Z-8722, 8730. The back side of the film was held by a black plate.
[0361] (11) Opacity (OD)
[0362] The transmission density based on white light was measured using Macbeth Densitometer TD-904. The measurement was performed at 5 points and the average value was taken as the OD value. The larger the value, the lower the transmittance.
[0363] (12) Apparent density (g / cm 3 )
[0364] Cut a 10 cm x 10 cm square sample from any part of the film and measure the thickness at 9 locations evenly with a micrometer. Calculate the weight per unit volume from the average value and the weight of the film as the apparent density. The number of measurements is set to 5 points, and the average value is used.
[0365] (13) Thickness of laminated white film
[0366] After the film pieces were fixed and molded with epoxy resin, they were cut with a slicer and the cross section of the film was observed with a transmission electron microscope. Two interfaces were observed in the cross section substantially parallel to the film surface according to the light and dark. The distance between the two interfaces and the film surface was measured from 10 photos, and the average value was used as the thickness of the laminated white film.
[0367] (14) Image quality optimization based on electronic photo printing
[0368] A film (sheet) cut into A4 size was fed into a multifunction printer: imagio MPC5001it manufactured by Ricoh Co., Ltd. to obtain a full-color test image on which an image forming material based on photo printing was placed. The image quality was evaluated as follows.
[0369] (Evaluation Criteria)
[0370] A: No wrinkles in the film, high-definition, high-quality images
[0371] B: Some parts of the image are not clear, but it is not a problem in practical use
[0372] C: Wrinkles and the like occurred in the film, and the image quality was not clear, which was poor overall.
[0373] (15) Optimization of text and image (toner image) stripping removal
[0374] A mixture of 95 parts by weight of an ultraviolet curable resin (2-hydroxy-3-phenoxypropyl acrylate) and 5 parts by weight of a photopolymerization initiator (trade name: Irgacure 184, manufactured by Chiba Specialty Chemicals Ltd.) was uniformly coated on the surface of the film fixed with the image forming material obtained in (14), and a glass plate was placed on the mixture, and ultraviolet rays were irradiated therefrom to form an ultraviolet curable resin layer. Thereafter, the glass plate and the film were peeled off. At this time, the ultraviolet curable resin layer formed was adhered to the glass plate side, and the text and image generated by the image forming material, etc. formed on the film surface could be transferred and maintained. The following evaluation was performed on the peeling and removal state of the text and image on the film surface at this time.
[0375] (Evaluation Criteria)
[0376] A: The image forming material on the film surface can be completely removed and can be reused as copy paper.
[0377] B: Only a part of the image forming material remains on the film surface, but the film can be repeatedly used as copy paper and has no practical problem.
[0378] C: Most of the image forming material remains on the film surface and the film cannot be reused as copy paper.
[0379] (16) Printing and conveying performance
[0380] 100 sheets of film (sheet) cut into A4 size were fed to a multifunction machine: imagio MPC5001it manufactured by Ricoh Co., Ltd., and the film (sheet) transport performance of the multifunction machine when 100 sheets of photo printing were continuously printed was evaluated as follows.
[0381] (Evaluation Criteria)
[0382] A: There was no clogging of the film (sheet) in the MFP. There was no overlap of the printed film (sheet) and it was confirmed that each sheet could be independently fed on the paper discharge table of the MFP.
[0383] B: Overlapping feeding of printed films (sheets) occasionally occurred, but within the range of no practical problem, there was no clogging of the films (sheets) in the multifunction machine, and continuous printing was confirmed on the paper discharge table of the multifunction machine.
[0384] C: Films (sheets) adhere to each other and multiple films become a block, so the multifunction machine cannot convey the film (sheet), or the film (sheet) is often blocked in the multifunction machine and continuous printing is impossible, or even if printing can be performed, the image quality is not clear and is poor overall.
[0385] (17) Note-taking
[0386] Five straight lines were drawn at intervals of 1 mm using a Uni pencil of hardness H manufactured by Mitsubishi Pencil Co., Ltd., and the following evaluation was performed by visual observation.
[0387] (Evaluation Criteria)
[0388] A: Individual straight lines can be distinguished.
[0389] B: The color of the lines is light and it is difficult to distinguish the lines.
[0390] C: Unable to draw a straight line.
[0391] (18) Functional layer appearance
[0392] The laminated white film was observed under a fluorescent lamp, and the appearance of the functional layer was visually evaluated as follows.
[0393] (Evaluation Criteria)
[0394] A: No defects in the functional layer, uniform appearance
[0395] B: Defects visible in part of the functional layer
[0396] C: Defects visible in most of the functional layer
[0397] [Example 1 Group]
[0398] As examples of the first embodiment, Examples 1-1 to 1-69 and Comparative Examples 1-1 to 1-2 will be described.
[0399] <Functional layer>
[0400] The compounds constituting the functional layer are as follows.
[0401] Antistatic agent (compound with ammonium group): (IA)
[0402] A polymer having a pyrrolidinium ring in the main chain and having the following composition
[0403] Diallyldimethylammonium chloride / dimethylacrylamide / N-methylolacrylamide=90 / 5 / 5 (mol%) Number average molecular weight: 30,000.
[0404] Antistatic agent (compound with ammonium group): (IB)
[0405] A polymer compound having a number average molecular weight of 50,000 and composed of a structural unit of the following formula (2) and a methanesulfonate ion as a counter ion.
[0406]
[0407] Release agent (compounds containing long-chain alkyl groups): (IIA)
[0408] In a four-necked flask, 200 parts by weight of xylene and 600 parts by weight of octadecyl isocyanate were added and heated under stirring. From the time when xylene began to reflux, 100 parts by weight of polyvinyl alcohol with an average degree of polymerization of 500 and a saponification degree of 88 mol% was added little by little every 10 minutes for about 2 hours. After the addition of polyvinyl alcohol was completed, reflux was further performed for 2 hours to terminate the reaction. After the reaction mixture was cooled to about 80°C, it was added to methanol. As a result, the reaction product was precipitated as a white precipitate. Therefore, the precipitate was filtered out, 140 parts by weight of xylene was added, and after heating to completely dissolve it, methanol was added again to precipitate it. After repeating this operation several times, the precipitate was washed with methanol, dried and crushed to obtain.
[0409] Release agent (condensation type silicone containing polyether): (IIB)
[0410] On the side chain of dimethyl silicone, in terms of molar ratio, with respect to 100 dimethyl siloxane, there is 1 polyethylene glycol (terminated with hydroxyl groups) with 8 ethylene glycol chains, and a number average molecular weight of 7000 polyether-containing silicone (when the siloxane bond of silicone is set to 1, the ether bond of the polyether group is 0.07 in terms of molar ratio). The low molecular weight component with a number average molecular weight of less than 500 is 3% by weight, and there is no vinyl group (vinyl silane) or hydrogen group (hydrogen silane) bonded to silicon. It should be noted that this compound is obtained by mixing and dispersing in water in a weight ratio of 1 polyether-containing silicone to 0.25 sodium dodecylbenzene sulfonate.
[0411] Release agent (wax): (IIC)
[0412] In an emulsifying device with a capacity of 1.5 L and equipped with a stirrer, a thermometer and a temperature controller, 300 g of oxidized polyethylene wax with a melting point of 105° C., an acid value of 16 mgKOH / g, a density of 0.93 g / mL and a number average molecular weight of 5000, 650 g of ion exchange water, 50 g of decaglycerol caprylate surfactant and 10 g of a 48 wt % potassium hydroxide aqueous solution were added. After replacement with nitrogen, the device was sealed and stirred at a high speed of 150° C. for 1 hour. The device was then cooled to 130° C., passed through a high-pressure homogenizer at 400 atmospheres, and cooled to 40° C. to form a wax emulsion.
[0413] Acrylic resin: (III)
[0414] Emulsified polymer of ethyl acrylate / n-butyl acrylate / N-methylol acrylamide / acrylic acid = 88 / 10 / 1 / 1 (wt%) (emulsifier: nonionic surfactant)
[0415] · Cross-linking agent (oxazoline compound): (IVA)
[0416] Epocros (registered trademark), an acrylic polymer having an oxazoline group and a polyalkylene oxide chain (oxazoline group content = 4.5 mmol / g, manufactured by Nippon Shokubai Co., Ltd.)
[0417] · Cross-linking agent (isocyanate compound): (IVB)
[0418] 1000 parts by weight of hexamethylene diisocyanate was stirred at 60°C, and 0.1 parts by weight of tetramethylammonium octanoate as a catalyst was added. After 4 hours, 0.2 parts by weight of phosphoric acid was added to stop the reaction, and an isocyanurate type polyisocyanate composition was obtained. 100 parts by weight of the obtained isocyanurate type polyisocyanate composition, 42.3 parts by weight of methoxy polyethylene glycol with a number average molecular weight of 400, and 29.5 parts by weight of propylene glycol monomethyl ether acetate were added, and kept at 80°C for 7 hours. After that, the temperature of the reaction liquid was kept at 60°C, and 35.8 parts by weight of methyl isobutyrylacetate, 32.2 parts by weight of diethyl malonate, and 0.88 parts by weight of a 28% by weight methanol solution of sodium methoxide were added, and kept for 4 hours. 58.9 parts by weight of n-butanol was added, and the reaction liquid temperature was kept at 80°C for 2 hours, and then 0.86 parts by weight of 2-ethylhexyl acid phosphate was added to obtain a blocked polyisocyanate based on active methylene.
[0419] · Cross-linking agent (hexamethoxymethylol melamine): (IVC)
[0420] [Example 1-1]
[0421] 80 parts by weight of polyethylene terephthalate chips with an intrinsic viscosity of 0.67 dl / g and 20 parts by weight of crystalline polypropylene homopolymer chips with a melt flow index of 10 ml / 10 minutes as the middle layer were fed into a main twin-screw extruder with a vent set at 280°C. Polyethylene terephthalate chips with an intrinsic viscosity of 0.66 dl / g and containing 50% by weight of titanium oxide particles with an average particle size of 0.32 μm as the surface layer were added. 15 parts by weight of small pieces, 15 parts by weight of crystalline polypropylene homopolymer small pieces with a melt flow index of 8 ml / 10 minutes, 10 parts by weight of polyethylene terephthalate small pieces with an intrinsic viscosity of 0.66 dl / g containing 3.5% by weight of silica particles with an average particle size of 4.1 μm, and 60 parts by weight of polyethylene terephthalate small pieces with an intrinsic viscosity of 0.69 dl / g were fed into a secondary twin-screw extruder with a vent set at 280° C. The extruder was co-extruded with a layer structure of two kinds of three layers (surface layer / middle layer / surface layer) by means of a gear pump and a filter, and the polymer from the main extruder became the middle layer and the polymer from the secondary extruder became the surface layer, and the extruded sheet was extruded from the nozzle, and the sheet was rapidly cooled and solidified on a cooling roll set at a surface temperature of 30° C. by an electrostatic application densification method, thereby obtaining a substantially amorphous sheet with a thickness of 887 μm.
[0422] The obtained amorphous sheet was stretched 3.1 times in the longitudinal direction at 92°C, and then the aqueous coating liquid 1 shown in the following Table 7 was coated on both sides of the longitudinally stretched film so that the film thickness of the functional layer (after drying) became 0.10 μm. The film was introduced into a tentering machine, and then stretched to 3.8 times in the transverse direction at 120°C, and then heat treated at 235°C for 10 seconds and relaxed in the transverse direction by 10% to obtain a laminated white film with a thickness of 6 μm (surface layer) / 62 μm (middle layer) / 6 μm (surface layer) and a total thickness of 74 μm.
[0423] The obtained laminated white film was evaluated and found to have good image quality, good text and image peeling and removal, good printing and transporting properties, good writing properties, and good functional layer appearance. The properties of the film are shown in Tables 4 and 8 below.
[0424] [Examples 1-2 to 1-4]
[0425] A laminated white thin film was obtained in the same manner as in Example 1-1 except that the film thickness of the functional layer (after drying) was changed as shown in Table 1.
[0426] The obtained laminated white film was shown in Tables 4 and 8 below, and had an improved image quality and good writing properties.
[0427] [Examples 1-5 to 1-14]
[0428] A laminated white film was obtained in the same manner as in Example 1-1 except that the composition of the coating solution of the functional layer was changed. The production conditions in each example are shown in Table 1 below, and the composition of the coating solution of the functional layer is shown in Table 7 below.
[0429] The obtained polyester film was shown in Tables 4 and 8 below, and had excellent image quality and good writing properties.
[0430] [Examples 1-15]
[0431] A laminated white film with a thickness of 75 μm was obtained in the same manner as in Example 1-1 except that 40 parts by weight of polyethylene terephthalate chips with an intrinsic viscosity of 0.63 dl / g, 15 parts by weight of crystalline polypropylene homopolymer chips with a melt flow index of 7 ml / 10 minutes, and a mixed raw material obtained by mixing the edge portion produced during the polyester production of Example 1-1 and the recycled product of the edge portion of the master roll at a ratio of 45% by weight as the middle layer. The thickness of each layer of the obtained film was 6 μm / 63 μm / 6 μm. The total amount of polypropylene from the crystalline polypropylene homopolymer chips and the recycled product in the middle layer was 24% by weight.
[0432] The obtained laminated white film was evaluated and found to have good image quality, good text and image peeling and removal, good printing and transporting properties, good writing properties, and good functional layer appearance. The properties of the film are shown in Tables 4 and 8 below.
[0433] [Examples 1-16 to 1-18]
[0434] A laminated white film was obtained in the same manner as in Example 1-15 except that the film thickness of the functional layer (after drying) was changed as shown in Table 1. The obtained laminated white film had an improved image quality and good writing properties as shown in Tables 4 and 8 below.
[0435] [Examples 1-19 to 1-27]
[0436] A laminated white film was obtained in the same manner as in Example 1-15 except that the composition of the coating solution of the functional layer was changed. The production conditions in each example are shown in Table 1 below, and the composition of the coating solution of the functional layer is shown in Table 7 below.
[0437] The obtained polyester film was shown in Tables 4 and 8 below. The image quality was improved, the characters and images were removed by peeling, and the printing and conveying properties and writing properties were good.
[0438] [Example 1-28]
[0439] A laminated white film having a thickness of 75 μm was obtained in the same manner as in Example 1-1 except that 3 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.66 dl / g, 10 parts by weight of crystalline polypropylene homopolymer chips having a melt flow index of 10 ml / 10 minutes, and 87% by weight of a mixed raw material obtained by mixing the edge portion produced during the polyester production of Example 1-1 and the recycled product of the edge portion of the master roll as the intermediate layer. The thickness of each layer of the obtained film was 6 μm / 63 μm / 6 μm.
[0440] The obtained laminated white film was evaluated and found to be excellent in terms of text and image peeling removal, printing transportability, writing properties, and functional layer appearance. The properties of the film are shown in Tables 4 and 8 below.
[0441] [Examples 1-29 to 1-31]
[0442] A laminated white film was obtained in the same manner as in Example 1-28 except that the film thickness of the functional layer (after drying) was changed as shown in Table 1. The obtained laminated white film had an improved image quality and good writing properties as shown in Tables 4 and 8 below.
[0443] [Examples 1-32 to 1-40]
[0444] A laminated white film was obtained in the same manner as in Example 1-28 except that the composition of the coating solution of the functional layer was changed. The production conditions in each example are shown in Table 1 below, and the composition of the coating solution of the functional layer is shown in Table 7 below.
[0445] The obtained polyester film was shown in Tables 4 and 8 below. The removal of characters and images was optimized, and the printing conveyability and writing properties were good.
[0446] [Example 1-41]
[0447] A laminated white film having a thickness of 75 μm was obtained in the same manner as in Example 1-15 except that 15 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.65 dl / g and containing 50% by weight of titanium oxide particles having an average particle size of 0.32 μm, 1.3 parts by weight of crystalline polypropylene homopolymer chips having a melt flow index of 8 ml / 10 minutes, 1.6 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.66 dl / g and containing 0.5% by weight of silica particles having an average particle size of 4.1 μm, and 82.1 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.68 dl / g were used as the surface layer. The thickness of each layer of the obtained film was 6 μm / 63 μm / 6 μm.
[0448] The obtained laminated white film was evaluated and found to have good image quality, good text and image peeling and removal, good printing and transport properties, and good functional layer appearance. The properties of the film are shown in Tables 5 and 9 below.
[0449] [Examples 1-42 to 1-44]
[0450] A laminated white film was obtained in the same manner as in Example 1-41 except that the film thickness of the functional layer (after drying) was changed as shown in Table 2. The obtained laminated white film had an improved image quality and good writing properties as shown in Tables 5 and 9 below.
[0451] [Examples 1-45 to 1-53]
[0452] A laminated white film was obtained in the same manner as in Example 1-41 except that the composition of the coating solution of the functional layer was changed. The production conditions in each example are shown in Table 2 below, and the composition of the coating solution of the functional layer is shown in Table 7 below.
[0453] The obtained polyester film was shown in the following Tables 5 and 9, and had excellent image quality, excellent text and image peeling and removal, and good printing and conveying properties.
[0454] [Example 1-54]
[0455] A laminated white film having a thickness of 75 μm was obtained in the same manner as in Example 1-15 except that 15 parts by weight of a polyethylene terephthalate chip having an intrinsic viscosity of 0.65 dl / g and containing 50% by weight of titanium oxide particles having an average particle size of 0.32 μm, 0.5 parts by weight of a crystalline polypropylene homopolymer chip having a melt flow index of 8 ml / 10 minutes, 10 parts by weight of a polyethylene terephthalate chip having an intrinsic viscosity of 0.66 dl / g and containing 3.5% by weight of silica particles having an average particle size of 4.1 μm, and 74.5 parts by weight of a polyethylene terephthalate chip having an intrinsic viscosity of 0.68 dl / g were used as the surface layer and the coating solution was applied only to one side in the coating step after longitudinal stretching. The thickness of each layer of the obtained film was 6 μm / 63 μm / 6 μm.
[0456] The obtained laminated white film was evaluated for image quality optimization, text and image peeling and removal optimization, and writing properties on one side that was not coated with the coating liquid. Image quality was optimized, printing and transport properties and the appearance of the functional layer were good. The properties of the film are shown in the following Tables 5 and 9.
[0457] [Example 1-55]
[0458] A laminated white film having a thickness of 75 μm was obtained in the same manner as in Example 1-15 except that 15 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.66 dl / g and containing 50% by weight of titanium oxide particles having an average particle size of 0.12 μm, 15 parts by weight of crystalline polypropylene homopolymer chips having a melt flow index of 8 ml / 10 minutes, 10 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.66 dl / g and containing 3.5% by weight of silica particles having an average particle size of 4.1 μm, and 60 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.69 dl / g were used. The thickness of each layer of the obtained film was 6 μm / 63 μm / 6 μm.
[0459] The obtained laminated white film was evaluated and found to be excellent in terms of text and image peeling and removal, and good in printing and transporting properties, writing properties, and functional layer appearance. The properties of the film are shown in Tables 5 and 9 below.
[0460] [Examples 1-56 to 1-58]
[0461] Except for changing the film thickness of the functional layer (after drying) as shown in Table 2, the same method as in Example 1-55 was carried out to obtain a laminated white film.
[0462] The obtained laminated white film was shown in the following Tables 5 and 9, and had an improved image quality and good writing properties.
[0463] [Examples 1-59 to 1-67]
[0464] A laminated white film was obtained in the same manner as in Example 1-55 except that the composition of the coating solution of the functional layer was changed. The production conditions in each example are shown in Table 2 below, and the composition of the coating solution of the functional layer is shown in Table 7 below.
[0465] The obtained polyester film was shown in the following Tables 5 and 9, and was found to have good text and image peeling removal properties and good printing and conveying properties and writing properties.
[0466] [Example 1-68]
[0467] A laminated white film having a thickness of 75 μm was obtained in the same manner as in Example 1-15 except that 15 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.66 dl / g and containing 50% by weight of titanium oxide particles having an average particle size of 0.32 μm, 15 parts by weight of crystalline polypropylene homopolymer chips having a melt flow index of 8 ml / 10 minutes, and 70 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.66 dl / g and containing 5.0% by weight of silicon dioxide particles having an average particle size of 11.1 μm were used as the surface layer. The thickness of each layer of the obtained film was 6 μm / 63 μm / 6 μm.
[0468] The obtained laminated white film was evaluated and found to have good image quality, good printing and transporting properties, good writing properties, and good appearance of the functional layer. The properties of the film are shown in Tables 5 and 9 below.
[0469] [Example 1-69]
[0470] In the heat treatment step in the thin film forming step, the heat treatment temperature was set to 201° C. and the heat treatment was performed for 10 seconds. In the same manner as in Example 1-15, a laminated white film having a thickness of 75 μm and a thickness of 6 μm / 63 μm / 6 μm for each layer was obtained.
[0471] The obtained laminated white film was evaluated and found to have good printing and transporting properties, writing properties and functional layer appearance. The properties of the film are shown in Tables 5 and 9 below.
[0472] [Comparative Example 1-1]
[0473] In Example 1-1, a polyester film was obtained in the same manner as in Example 1-1 except that a polyethylene terephthalate small piece was used instead of a crystalline polypropylene homopolymer small piece and no functional layer was provided. The obtained polyester film was inferior in any of the properties including image quality optimization, text and image peeling and removal optimization, print transportability, and writing properties as shown in Tables 6 and 10.
[0474] [Comparative Example 1-2]
[0475] A laminated white film was obtained in the same manner as in Example 1-1 except that the composition of the coating solution of the functional layer was changed. The production conditions of Comparative Example 1-2 are shown in Table 3 below, and the composition of the coating solution of the functional layer is shown in Table 7 below.
[0476] The obtained polyester film was shown in the following Tables 6 and 10. The image quality was good but the printing and transporting properties were poor.
[0477] [Table 1]
[0478]
[0479] [Table 2]
[0480]
[0481] [Table 3]
[0482]
[0483] [Table 4]
[0484]
[0485] [Table 5]
[0486]
[0487] [Table 6]
[0488]
[0489] [Table 7]
[0490]
[0491] [Table 8]
[0492]
[0493] [Table 9]
[0494]
[0495] [Table 10]
[0496]
[0497] [Reference Example 2 Group]
[0498] As examples of the second embodiment, reference examples 2-1 to 2-6 and comparative examples 2-1 and 2-2 will be described.
[0499] [Reference Example 2-1]
[0500] A mixed raw material prepared by mixing 80 parts by weight of polyethylene terephthalate chips with an intrinsic viscosity of 0.67 dl / g and 20 parts by weight of crystalline polypropylene homopolymer chips with a melt flow index of 10 ml / 10 minutes as an intermediate layer was fed into a main twin-screw extruder with a vent set at 280°C.
[0501] Furthermore, a mixed raw material prepared by mixing 15 parts by weight of polyethylene terephthalate chips with an intrinsic viscosity of 0.66 dl / g and containing 50% by weight of titanium oxide particles with an average particle size of 0.32 μm as a surface layer, 15 parts by weight of crystalline polypropylene homopolymer chips with a melt flow index of 8 ml / 10 minutes, 10 parts by weight of polyethylene terephthalate chips with an intrinsic viscosity of 0.66 dl / g and containing 3.5% by weight of silicon dioxide particles with an average particle size of 4.1 μm, and 60 parts by weight of polyethylene terephthalate chips with an intrinsic viscosity of 0.69 dl / g was fed into a secondary twin-screw extruder with a vent set at 280°C.
[0502] With the aid of a gear pump and a filter, co-extrusion is performed with two types of three-layer (surface layer / middle layer / surface layer) structures, so that the polymer from the main extruder becomes the middle layer and the polymer from the sub-extruder becomes the surface layer and is extruded from a nozzle, and electrostatic densification is used, and the film is rapidly cooled and solidified on a cooling roller whose surface temperature is set to 30°C to obtain an unstretched film with a thickness of 887 μm.
[0503] The obtained unstretched sheet was stretched 3.1 times at 92°C in the longitudinal direction and then introduced into a tentering machine. Subsequently, it was stretched to 3.8 times at 120°C in the transverse direction, and then heat treated at 235°C for 10 seconds and relaxed 10% in the transverse direction to obtain a biaxially oriented laminated white polyester film with a thickness of 6μm (surface layer) / 62μm (middle layer) / 6μm (surface layer) and a total thickness of 74μm.
[0504] The obtained laminated white polyester film was evaluated and found to have good image quality, good text and image peeling and removal, and good writing properties. The properties of the film are shown in Tables 12 and 13 below.
[0505] [Reference Example 2-2]
[0506] As the middle layer, the following mixed raw materials were used: 40 parts by weight of polyethylene terephthalate chips with an intrinsic viscosity of 0.63 dl / g, 15 parts by weight of crystalline polypropylene homopolymer chips with a melt flow index of 7 ml / 10 minutes, and 45% by weight of the recycled edge and master roll edge produced during the polyester production of Reference Example 2-1. In the same manner as Reference Example 2-1, a biaxially oriented laminated white polyester film with a thickness of 75 μm was obtained. The thickness of each layer of the obtained film was 6 μm / 63 μm / 6 μm. It should be noted that the total amount of polypropylene from the crystalline polypropylene homopolymer chips and the recycled product in the middle layer was 24% by weight.
[0507] The obtained laminated white polyester film was evaluated and found to have good image quality, good text and image peeling and removal, and good writing properties. The properties of the film are shown in Tables 12 and 13 below.
[0508] [Reference Example 2-3]
[0509] As the intermediate layer, a biaxially oriented laminated white polyester film having a thickness of 75 μm was obtained in the same manner as in Reference Example 2-1 except that a mixed raw material was used: 3 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.66 dl / g, 10 parts by weight of crystalline polypropylene homopolymer chips having a melt flow index of 10 ml / 10 minutes, and 87% by weight of recycled products of the edge portions and the edge portions of the master roll produced during the polyester production of Reference Example 2-1. The thickness of each layer of the obtained film was 6 μm / 63 μm / 6 μm.
[0510] The obtained laminated white polyester film was evaluated and found to be excellent in both text and image peeling removal and writing properties. The properties of the film are shown in Tables 12 and 13 below.
[0511] [Reference Example 2-4]
[0512] As the surface layer, a biaxially oriented laminated white polyester film having a thickness of 75 μm was obtained in the same manner as in Reference Example 2-1 except that a mixed raw material was used: 15 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.66 dl / g and containing 50% by weight of titanium oxide particles having an average particle size of 0.12 μm, 15 parts by weight of crystalline polypropylene homopolymer chips having a melt flow index of 8 ml / 10 minutes, 10 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.66 dl / g and containing 3.5% by weight of silica particles having an average particle size of 4.1 μm, and 60 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.69 dl / g. The thickness of each layer of the obtained film was 6 μm / 63 μm / 6 μm.
[0513] The obtained laminated white polyester film was evaluated and found to be excellent in both text and image peeling removal and writing properties. The properties of the film are shown in Tables 12 and 13 below.
[0514] [Reference Example 2-5]
[0515] As the surface layer, a biaxially oriented laminated white polyester film having a thickness of 74 μm was obtained in the same manner as in Reference Example 2-2 except that a mixed raw material was used: 15 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.66 dl / g and containing 50% by weight of titanium oxide particles having an average particle size of 0.32 μm, 1.3 parts by weight of crystalline polypropylene homopolymer chips having a melt flow index of 8 ml / 10 minutes, 1.6 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.66 dl / g and containing 0.5% by weight of silica particles having an average particle size of 4.1 μm, and 82.1 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.69 dl / g. The thickness of each layer of the obtained film was 6 μm / 62 μm / 6 μm.
[0516] The obtained laminated white polyester film was evaluated and found to have good image quality. The properties of the film are shown in Tables 12 and 13 below.
[0517] [Reference Example 2-6]
[0518] As the surface layer, a biaxially oriented laminated white polyester film having a thickness of 75 μm was obtained in the same manner as in Reference Example 2-2 except that a mixed raw material was used: 15 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.65 dl / g and containing 50% by weight of titanium oxide particles having an average particle size of 0.32 μm, 0.5 parts by weight of crystalline polypropylene homopolymer chips having a melt flow index of 8 ml / 10 minutes, 10 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.66 dl / g and containing 3.5% by weight of silica particles having an average particle size of 4.1 μm, and 74.5 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.68 dl / g. The thickness of each layer of the obtained film was 6 μm / 63 μm / 6 μm.
[0519] The obtained laminated white polyester film was evaluated and found to have good image quality. The properties of the film are shown in Tables 12 and 13 below.
[0520] [Comparative Example 2-1]
[0521] As the surface layer, a biaxially oriented laminated white polyester film having a thickness of 75 μm was obtained in the same manner as in Reference Example 2-2 except that a mixed raw material was used: 15 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.66 dl / g and containing 50% by weight of titanium oxide particles having an average particle size of 0.32 μm, 15 parts by weight of crystalline polypropylene homopolymer chips having a melt flow index of 8 ml / 10 minutes, and 70 parts by weight of polyethylene terephthalate chips having an intrinsic viscosity of 0.66 dl / g and containing 5.0% by weight of silicon dioxide particles having an average particle size of 11.1 μm. The thickness of each layer of the obtained film was 6 μm / 63 μm / 6 μm.
[0522] The obtained laminated white polyester film was shown in the following Tables 12 and 13, and the text and image peeling removal was poor.
[0523] [Comparative Example 2-2]
[0524] In the heat treatment step in the film forming step, the heat treatment temperature was set to 201° C. and the heat treatment was performed for 10 seconds. In the same manner as in Reference Example 2-2, a biaxially oriented laminated white polyester film having a thickness of 75 μm and a thickness of each layer of 6 μm / 63 μm / 6 μm was obtained.
[0525] The obtained laminated white polyester film was shown in Tables 12 and 13 below, and was poor in image quality optimization and text and image peeling and removal optimization.
[0526] [Table 11]
[0527]
[0528] [Table 12]
[0529]
[0530] [Table 13]
[0531]
Claims
1. A laminated white film, characterized in that: The apparent density is 0.7~1.3g / cm 3 , a polyester film having a thickness of 10 to 1000 μm, at least one side of which has a functional layer containing an antistatic agent, the polyester film having a polyester resin layer, the polyester resin layer containing a polyester as a main component resin, and a polymer incompatible with the polyester, the polyester being obtained by polycondensing an aromatic dicarboxylic acid and an aliphatic diol, the polymer incompatible with the polyester being polypropylene, and the polyester film containing the polymer incompatible with the polyester, thereby having fine cavities and being able to be used as an information printing medium, i.e., a recorded material, instead of paper; The functional layer contains a release agent in addition to the antistatic agent, the release agent contains a long-chain alkyl-containing compound, and the long-chain alkyl-containing compound is a compound having a straight-chain or branched alkyl group with more than 6 carbon atoms; the functional layer contains a cross-linked structure derived from a cross-linking agent, and the cross-linking agent is an oxazoline compound and / or an isocyanate compound; The polyester film contains metal compound particles, and the average particle size of the metal compound particles is 0.25 μm or more and 0.45 μm or less.
2. The laminated white film according to claim 1, characterized in that: The functional layer contains the release agent at a ratio of 3% by weight or more in the functional layer.
3. The laminated white film according to claim 1 or 2, characterized in that: The functional layer is a recorded layer.
4. The laminated white film according to claim 1 or 2, characterized in that: The polyester film comprises two surface layers and an intermediate layer, and the content of the polymer incompatible with polyester in the intermediate layer is 8% by weight or more.
5. The laminated white film according to claim 4, characterized in that: The polyester film contains silica particles or organic particles or both as particles other than the metal compound particles.
6. The laminated white film according to claim 1 or 2, characterized in that: The polyester film has two surface layers and a middle layer. The two surface layers are formed of a resin composition containing polyester, a polymer incompatible with the polyester, metal compound particles, and silica particles or organic particles or both, and the arithmetic mean roughness (Ra) of the surface layer is 950 nm or less.
7. The laminated white film according to claim 1 or 2, characterized in that: The polyester film is a stretched film.
8. The laminated white film according to claim 1 or 2, characterized in that: The polyester film contains a polymer incompatible with polyester in an amount of 1% by weight or more and 70% by weight or less.
9. The laminated white film according to claim 1, characterized in that: The content of the metal compound particles in the polyester film is 1% by weight or more and 30% by weight or less.
10. The laminated white film according to claim 5, characterized in that: The average particle size of the silica particles or organic particles is greater than 0.50 μm and is less than or equal to 15.0 μm.
11. The laminated white film according to claim 5, characterized in that: The content of the silica particles or the organic particles in the polyester film is 0.005% by weight or more and 5% by weight or less.
12. The laminated white film according to claim 6, wherein: The arithmetic mean roughness (Ra) of the surface layer is 350 nm or more. 13 . A laminated white film comprising an image forming substance on a functional layer of the laminated white film according to claim 1 .
14. The laminated white film according to claim 13, wherein: A resin layer is provided on the image forming material or on the functional layer.
15. The laminated white film according to claim 14, wherein: The resin layer is formed by laminating the image forming material or the functional layer in a releasable manner.
16. The laminated white film according to claim 14, wherein: The resin layer is a curable resin layer. 17 . A record-receiving material comprising an image forming substance on a functional layer of the laminated white film according to claim 1 .
18. The recorded material according to claim 17, wherein: A resin layer is provided on the image forming material or on the functional layer.
19. The recorded material according to claim 18, wherein: The resin layer is formed by laminating the image forming material or the functional layer in a releasable manner.
20. The recorded material according to claim 18, wherein The resin layer is a curable resin layer.
Citation Information
Patent Citations
Synthetic paper excellent in printability
JP1998204196A
Electrophotographic paper, manufacturing method for it, electrophotographic image forming method
JP2005234162A
White laminated film and recording material
CN110325363A
Fine cellular polyester film
JP2001049001A